Battery cells, batteries and power consuming devices

By adjusting the mass content of the silicon-carbon composite in the negative active substance in the battery cells and using an electrolyte system with high content of lithium fluorophosphate, the problem of degradation of the power performance of the battery during later discharge is solved, and higher discharge power performance is achieved.

JP2025507262AActive Publication Date: 2025-03-18CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024543854
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2024-03-27
Filing Date
2024-04-09
Publication Date
2025-03-18
Estimated Expiration
2044-04-09

AI Technical Summary

Technical Problem

The discharge power of existing battery cells is poor when discharged at a later stage, especially when the SOC is ≤10%, the battery's power performance is significantly reduced.

Method used

By adjusting the mass content of the silicon-carbon composite in the negative active material (the mass content of silicon element is between 0.3% and 10.0%), and combining with a suitable electrolyte system, the lithium salt contains lithium fluorophosphate, and the mass content accounts for 15% to 20% of the total mass of the electrolyte.

Benefits of technology

It effectively reduces the internal resistance of the battery at the end of discharge and improves the discharge power performance, especially during low SOC periods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025507262000001_ABST
    Figure 2025507262000001_ABST
Patent Text Reader

Abstract

The present application relates to a battery cell, a battery and a power consuming device, the battery cell comprising an electrolyte, a positive electrode plate, a negative electrode plate and a separator, the electrolyte comprising a lithium salt, the lithium salt comprising lithium hexafluorophosphate, the mass content of the lithium hexafluorophosphate relative to the total mass of the electrolyte being 15% to 20%, the positive electrode plate comprising a positive electrode collector and a positive electrode film layer disposed on at least one side of the positive electrode collector and containing a positive electrode active material, the negative electrode plate comprising a negative electrode collector and a negative electrode film layer disposed on at least one side of the negative electrode collector and containing a negative electrode active material, the negative electrode active material further comprising a carbon-based material and a silicon-carbon composite, the mass content of silicon element in the silicon-carbon composite relative to the total mass of the negative electrode active material being 0.3% or more and 10.0% or less, and the separator is disposed between the positive electrode plate and the negative electrode plate. The discharge power of the battery cell described in the present application can be improved in the later stages of discharge.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims priority to Chinese patent application No. 202311421105.X, entitled "Battery Cell, Battery and Power Consumption Device," proposed on October 30, 2023, the entire contents of which are incorporated herein by reference.

[0002] This application claims priority to PCT patent application PCT / CN2024 / 084136, entitled “Battery Cell, Battery and Power Consuming Device,” proposed on March 27, 2024, the entire contents of which are incorporated herein by reference.

[0003] The present application relates to the field of rechargeable batteries, and in particular to battery cells, batteries and power consuming devices. [Background technology]

[0004] Due to the characteristics of high capacity, long life, etc., battery cells are widely used in electronic devices, such as mobile phones, notebook computers, battery cars, electric cars, electric airplanes, electric steamships, electric toy cars, electric toy steamships, electric toy airplanes and electric tools, etc. As the battery field has progressed greatly, the requirements for the performance of battery cells have also increased.

[0005] However, current battery cells have relatively poor discharge power in the later stages of discharge. Summary of the Invention

[0006] The present application provides a battery cell, a battery and a power consuming device, which can improve the discharge power of the battery cell described in the present application in the later stage of discharge.

[0007] According to a first aspect, an embodiment of the present application proposes a battery cell, the battery cell including an electrolyte, a positive electrode plate, a negative electrode plate, and a separator, the electrolyte including a lithium salt, the lithium salt including lithium hexafluorophosphate, the mass content of the lithium hexafluorophosphate relative to the total mass of the electrolyte being 15% to 20%, the positive electrode plate including a positive electrode collector and a positive electrode film layer disposed on at least one side of the positive electrode collector and containing a positive electrode active material, the negative electrode plate including a negative electrode collector and a negative electrode film layer disposed on at least one side of the negative electrode collector and containing a negative electrode active material, the negative electrode active material further including a carbon-based material and a silicon-carbon composite, the mass content of silicon element in the silicon-carbon composite relative to the total mass of the negative electrode active material being 0.3% or more and 10.0% or less, and the separator is disposed between the positive electrode plate and the negative electrode plate.

[0008] As a result, in the embodiment of the present application, by adjusting the mass content of the silicon-carbon composite of the negative electrode active material (the mass content of silicon element in the silicon-carbon composite is 0.3% or more and 10.0% or less) and combining it with an appropriate electrolyte system (the mass content of lithium hexafluorophosphate is 15% to 20%), the internal resistance at the end of discharge of the battery can be reduced and the discharge power performance can be improved.

[0009] In some embodiments, the mass content of silicon element in the silicon-carbon composite relative to the total mass of the negative electrode active material is 4.0% or more and 7.0% or less. By setting the mass content of silicon element in the silicon-carbon composite within the above range, the energy density of the battery cell can be further increased, and the carbon element in the silicon-carbon composite can act to mitigate the expansion of the silicon element, so that the expansion of the silicon-carbon composite does not become excessive. By combining it with the above electrolyte system, the internal resistance at the end of discharge of the battery can be significantly reduced and the discharge power performance can be improved.

[0010] In some embodiments, the mass content of the silicon-carbon composite is 0.4% to 14.5% based on the total mass of the negative electrode active material. When the negative electrode active material satisfies the above mass content of silicon element, the discharge power at low SOC of the battery can be further improved.

[0011] In some embodiments, the mass content of the silicon-carbon composite is 5.75% to 10% based on the total mass of the negative electrode active material. When the mass content of silicon element is within the above content range, the discharge power at low SOC can be further improved.

[0012] In some embodiments, the carbon-based material includes at least one of synthetic graphite and natural graphite.

[0013] In some embodiments, the carbon-based material comprises synthetic graphite.

[0014] In some embodiments, the electrolyte further comprises a cyclic carbonate, and the ratio of the mass content of the cyclic carbonate to the mass content of lithium hexafluorophosphate, based on the total mass of the electrolyte, is (0.60-2.50): 1, and optionally (1.00-1.65): 1. The presumable beneficial effects are as follows: when the ratio of the mass content of the cyclic carbonate to the mass content of lithium hexafluorophosphate is in the above range, it is favorable for sufficiently dissociating more lithium ions from lithium hexafluorophosphate, so that even at the end of discharge with a low SOC, more lithium ions can be contained in the electrolyte system, and the lithium ions can be continuously dissociated with the progress of the battery reaction, thereby improving the power performance of the battery.

[0015] In some embodiments, the mass content of the cyclic carbonate is 10% to 41%, and optionally 20% to 30%, and the cyclic carbonate has a high dielectric constant and high ionic conductivity and can form a stable SEI film on the surface of the negative electrode active material, which is advantageous for the power performance of the battery at the end of discharge.

[0016] In some embodiments, the cyclic carbonate comprises at least one of ethylene carbonate EC, propylene carbonate PC, and butylene carbonate BC.

[0017] In some embodiments, the electrolyte further comprises a chain carbonate, and the ratio of the mass content of the chain carbonate to the mass content of the cyclic carbonate, based on the total mass of the electrolyte, is (0.9-6):1, and optionally (1.5-2.65):1. When the mass content ratio of the chain carbonate to the cyclic carbonate satisfies the above range, it is possible to improve both the viscosity and ionic conductivity of the electrolyte, and to enhance the kinetic performance of lithium ions.

[0018] In some embodiments, the mass content of the chain carbonate is 35% to 65%, and / or the chain carbonate includes at least one of ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dimethyl carbonate (DMC). The viscosity of the chain carbonate is relatively low, which contributes to sufficient dissolution of lithium hexafluorophosphate at a high content, and is advantageous for lithium ions ionized from lithium hexafluorophosphate to rapidly move between the positive and negative electrodes. The combined use of the chain carbonate and the cyclic carbonate also contributes to increasing the electrochemical stability of the electrolyte system and effectively reducing side reactions of the electrolyte.

[0019] In some embodiments, the electrolyte further comprises a fluorinated cyclic carbonate, which is involved in the formation of an SEI film on the surface of the negative electrode active material, can improve the film components and properties, and can effectively protect the negative electrode active material; in particular, when the negative electrode contains silicon, due to the characteristics of silicon expansion, it is necessary to further optimize the film composition of the SEI film formation, which is adjusted by adjusting the relative proportion of the film-forming additive in the electrolyte; the film formed by the involvement of the fluorinated cyclic carbonate can improve the flexibility of the SEI film, and can improve the collapse of the structure caused by the release of a large amount of lithium ions in a short time at the end of discharge; and the fluorinated cyclic carbonate has a certain desolvation ability, which is favorable to the migration of lithium ions, can improve the DCR at low SOC, and can increase the discharge power.

[0020] In some embodiments, the fluorinated cyclic carbonate comprises at least one of monofluoroethylene carbonate FEC, bisfluoroethylene carbonate DFEC, and trifluoropropylene carbonate TFPC, and optionally the fluorinated cyclic carbonate comprises monofluoroethylene carbonate FEC.

[0021] In some embodiments, the ratio of the mass content of the fluorinated cyclic carbonate to the total mass of the electrolyte and the mass content of the silicon element is (0.01-9.5): 1, and optionally (0.01-0.15): 1. The combination of the fluorinated cyclic carbonate with the above content and the negative electrode plate can significantly improve the power performance of the battery cell.

[0022] In some embodiments, the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of the lithium salt, based on the total mass of the electrolyte, is (0.005 to 0.30): 1, and optionally (0.005 to 0.03): 1. When the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of the lithium salt is within the above range, not only can the flexibility of the SEI membrane, and improvements in ionic conductivity and electronic conductivity performance be simultaneously achieved, but also the discharge power of the battery can be increased by reducing the DCR.

[0023] In some embodiments, the mass content of the fluorinated cyclic carbonate is 0.05%-5.80%, and optionally 0.1%-1.0%, based on the total mass of the electrolyte. Since the carbon element in the silicon-carbon composite can effectively mitigate the expansion of the silicon element, the fluorinated cyclic carbonate with a relatively low content can also significantly improve the discharge power performance of the battery cell.

[0024] In some embodiments, the lithium salt further comprises at least one of a fluorine-containing inorganic phosphate and a fluorine-containing inorganic borate, which can participate in the formation of inorganic components in the SEI film, which is beneficial for enhancing the ionic and electronic conductivity performance of the SEI film, and the interfacial ionic impedance of the formed SEI film is relatively low, which is beneficial for the transmission of lithium ions, and can improve the DCR at low SOC.

[0025] In some embodiments, the mass content of the fluorine-containing inorganic phosphate is 0.05%-0.50%, and optionally 0.10%-0.30%, based on the total mass of the electrolyte. The above content of the fluorine-containing inorganic phosphate combined with the negative electrode plate can significantly improve the power performance of the battery cell.

[0026] In some embodiments, the mass content of the fluorine-containing inorganic borate is 0.05%-0.50%, and optionally 0.10%-0.30%, based on the total mass of the electrolyte. The above content of the fluorine-containing inorganic borate combined with the negative electrode plate can significantly improve the power performance of the battery cell.

[0027] In some embodiments, the fluorine-containing inorganic phosphate comprises lithium difluorophosphate LiPO2F2 and / or the fluorine-containing inorganic borate comprises at least one of lithium tetrafluoroborate LiBF4 and lithium difluoro(oxalato)borate LiDFOB.

[0028] In some embodiments, the electrolyte further comprises an additive, the additive comprising at least one of 1,3-propane sultone PS, vinylene carbonate VC, and lithium fluorosulfonate LiSO3F, and the ratio of the mass content of 1,3-propane sultone PS, the mass content of vinylene carbonate VC, and the mass content of lithium fluorosulfonate LiSO3F based on the total mass of the electrolyte is (0.050-0.300):(0.100-0.500):(0.001-0.300). When the ratio of the mass content of 1,3-propane sultone PS, the mass content of vinylene carbonate VC, and the mass content of lithium fluorosulfonate LiSO3F is within the above range, the above components can essentially participate in the formation of an SEI film on the surface of the negative electrode active material, and the SEI film can effectively mitigate the expansion of the silicon-carbon composite.

[0029] In some embodiments, the mass content of 1,3-propane sultone PS is between 0.1% and 1.0%, and / or the mass content of vinylene carbonate VC is between 0.1% and 1.0%, and / or the mass content of lithium fluorosulfonate LiSO3F is between 0.1% and 1.0%.

[0030] In some embodiments, the battery cell has a retention coefficient between 1 g / Ah and 2.5 g / Ah, optionally between 1.0 g / Ah and 1.5 g / Ah.

[0031] The liquid retention coefficient of a battery cell can reflect the liquid retention capacity of the electrolyte. When the liquid retention coefficient of a battery cell is within the above range, the electrolyte can have a relatively good infiltration effect on the positive electrode plate and the negative electrode plate, and there is a certain gap between the negative electrode plate and the separator, which provides an expansion space for the volume expansion of the silicon-carbon composite, and reduces the risk of the entire battery swelling.

[0032] In some embodiments, the porosity of the separator is 30% to 40%. In the battery cell of the present application, since the amount of lithium hexafluorophosphate added is relatively high, the viscosity of the entire electrolyte is relatively high, and the porosity of the separator is relatively high, which is advantageous for the relatively viscous electrolyte to pass through the separator, allowing smooth movement of lithium ions.

[0033] In some embodiments, the separator comprises an organic substrate and a coating disposed on at least one side of the organic substrate, the coating comprising a heat-resistant layer and an organic layer, the heat-resistant layer being disposed on a surface of the organic substrate and the organic layer being disposed on a surface of the heat-resistant layer facing away from the organic substrate. The separator in combination with the electrolyte and a negative electrode plate can significantly improve the power performance of a battery cell.

[0034] In some embodiments, the organic layer comprises a non-fluorinated polymer.The separator in combination with the electrolyte and negative electrode plate can significantly improve the power performance of the battery cell.

[0035] In some embodiments, the non-fluorinated polymer comprises a polyacrylate layer.The separator in combination with the electrolyte and negative electrode plate can significantly improve the power performance of the battery cell.

[0036] In some embodiments, the separator includes an organic substrate and a coating disposed on at least one side of the organic substrate, the coating including a ceramic layer and / or a polyacrylate layer, and optionally the coating includes a ceramic layer and a polyacrylate layer, and optionally the ceramic layer is disposed on a surface of the organic substrate and the polyacrylate layer is disposed on a surface of the ceramic layer that is away from the organic substrate. By disposing the polyacrylate layer on the outer surface of the separator, the outer surface of the separator has a certain flexibility, which can effectively mitigate the volumetric expansion or contraction of the silicon-carbon composite, and enhance the structural stability of the entire electrode assembly.

[0037] In some embodiments, the thickness of the organic substrate is 6.6 μm to 7.6 μm. When the thickness of the organic substrate is in the above range, the lithium ion transfer rate in the negative electrode plate and the transfer rate in the separator can be basically matched, and the risk of deterioration of concentration polarization can be reduced, which is advantageous for improving discharge performance.

[0038] In some embodiments, the coating has a thickness of 1.5 μm to 2.5 μm. When the coating has a thickness in the above range, the lithium ion transfer rate in the negative electrode plate and the transfer rate in the separator can be basically matched, and the risk of deterioration of concentration polarization can be reduced, which is advantageous for improving discharge performance.

[0039] In some embodiments, the positive electrode active material has the molecular formula Li d Ni a Co b Mn c M (1-a-b-c) Y zA compound is included, where 0 < d ≤ 2.1, 0.6 < a < 1, 0 < b < 1, 0 < c < 1, and 0.6 < a + b + c < 1, 1.8 ≤ z ≤ 3.5. The M element contains at least one element among B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, Ce. The Y element contains at least one element among O and F. By combining the above positive electrode active material system with the above electrolyte and the negative electrode plate, the power performance of the battery cell can be significantly improved.

[0040] In some embodiments, 0.85 ≤ a ≤ 0.95. By combining the above positive electrode active material system with the above electrolyte and the negative electrode plate, the power performance of the battery cell can be significantly improved.

[0041] In some embodiments, the positive electrode active material contains at least one of single crystal particles and polycrystalline particles. By combining the above positive electrode active material system with the above electrolyte and the negative electrode plate, the power performance of the battery cell can be significantly improved.

[0042] In some embodiments, the positive electrode active material contains single crystal particles and polycrystalline particles. By combining the above positive electrode active material system with the above electrolyte and the negative electrode plate, the power performance of the battery cell can be significantly improved.

[0043] According to a second aspect, the present application further proposes a battery, and the battery includes a battery cell described in any one of the embodiments of the first aspect of the present application.

[0044] According to a third aspect, the present application further proposes a power consumption device, and this power consumption device includes a battery described in any one of the embodiments of the second aspect of the present application.

Brief Description of the Drawings

[0045] In order to more clearly explain the technical solutions of the embodiments of the present application, the following briefly introduces the drawings that need to be used in the embodiments of the present application. It is obvious that the drawings described below are only some embodiments of the present application, and those skilled in the art can also obtain other drawings based on the drawings without exerting creative efforts. [Figure 1] FIG. 1 is a schematic diagram of one embodiment of a battery cell of the present application. [Diagram 2] FIG. 2 is an exploded schematic diagram of an embodiment of the battery cell of FIG. 1. [Diagram 3] FIG. 1 is a schematic diagram of one embodiment of a battery module of the present application. [Figure 4] 1 is a schematic diagram of one embodiment of a battery pack of the present application. [Diagram 5] 5 is an exploded schematic view of the embodiment of the battery pack shown in FIG. 4. [Figure 6] 1 is a schematic diagram of one embodiment of a power consuming device that includes a battery cell of the present application as a power source.The drawings are not necessarily drawn to scale. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0046] Hereinafter, with appropriate reference to the drawings, embodiments specifically disclosing the battery cell, battery, and power consumption device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and duplicated description of structures that are actually the same may be omitted. This is to avoid the following description becoming unnecessarily long and to allow those skilled in the art to easily understand. Note that the drawings and the following description are provided to allow those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.

[0047] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the end values, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also contemplated. However, if 1 and 2 are listed as the minimum range values, and 3, 4, and 5 are listed as the maximum range values, the following ranges are all contemplated: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise specified, the numerical range "a-b" represents a shorthand representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" are already listed in this specification, and "0-5" is just a shorthand for combinations of these numbers. Also, expressing a parameter as an integer ≧2 is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0048] Unless otherwise stated, all the embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0049] Unless otherwise stated, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0050] Unless otherwise stated, all steps in this application may be performed in sequence or randomly, and preferably in sequence. For example, the method includes steps (a) and (b) to mean that the method may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, the method mentioned above may further include step (c) to mean that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.

[0051] Lithium-ion battery discharge is a process in which lithium ions are released from the negative electrode active material and embedded in the positive electrode active material via the electrolyte. In the battery field, the industry often uses the term "state of charge (abbreviated as SOC)" to reflect the remaining capacity of a battery after discharge. The value is defined as the percentage of the remaining capacity in the battery capacity, and the value ranges from 0 to 100%. When "SOC=0", the battery is completely discharged, and when "SOC=100%, the battery is fully charged.

[0052] The discharge process of lithium-ion batteries has a problem of insufficient "discharge power" in the later stage of discharge. For example, in the discharge process in which a battery is discharged to a state of charge (SOC) of ≦10% and then continues to be discharged to 0%, the power performance of the discharge is lower than that of the previous discharge, which reduces the power performance of the entire discharge process of the battery.

[0053] In view of the above problems, the present application proposes a battery cell, which includes a negative electrode plate advantageous for improving the later discharge power of the battery, and based on the negative electrode plate, combines an electrolyte advantageous for improving the later discharge power of the battery, and may further include a suitable separator and a positive electrode plate, and the power performance of the battery in the later discharge period (especially the discharge process from 10% to 0% SOC) is significantly improved.

[0054] Battery Cell A first aspect of the present application provides a battery cell, the battery cell including a positive electrode plate, a separator, a negative electrode plate, and an electrolyte. The positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector and containing a positive electrode active material, the electrolyte includes a lithium salt, the lithium salt includes lithium hexafluorophosphate, and the mass content of the lithium hexafluorophosphate relative to the total mass of the electrolyte is 15% to 20%. The negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one side of the negative electrode current collector and containing a negative electrode active material, the negative electrode active material further includes a carbon-based material and a silicon-carbon composite, and the mass content of silicon element in the silicon-carbon composite relative to the total mass of the negative electrode active material is 0.3% or more and 10.0% or less.

[0055] The negative electrode active material of the battery cell includes a carbon-based material that provides elemental carbon and a silicon-carbon composite that provides elemental silicon.

[0056] The carbon-based material providing the carbon element is mainly composed of carbon element and may contain silicon element at the same time, or may contain only carbon element, and the silicon-carbon composite providing the silicon element may contain silicon element, may contain carbon element at the same time, or may contain only silicon element. The negative electrode active material simultaneously contains a carbon-based material and a silicon-carbon composite, and the mass content of the silicon element in the silicon-carbon composite relative to the total mass of the negative electrode active material is 0.3% or more, and the following factors are taken into consideration. Compared with the carbon-based material, the silicon-carbon composite has silicon element and its lithium absorption / release voltage plateau is relatively high, so that even at a low SOC (e.g., SOC≦10%), the silicon-carbon composite can continue to participate in discharge, which makes up for the shortcomings that the carbon-based material is difficult / impossible to continue discharging at a low SOC, improves the direct current internal resistance DCR during the discharge process of the battery, and further improves the power performance during the discharge process of the battery.

[0057] In the battery cell of the present application, the negative electrode active material is mainly made of a carbon-based material and is added with a small amount of silicon-carbon composite, that is, the mass content of silicon element in the negative electrode active material is smaller than the mass content of carbon element, and the mass content of silicon element in the silicon-carbon composite relative to the total mass of the negative electrode active material is not more than 10.0%, taking into consideration the following reasons:

[0058] Although the lithium absorption and release potential of silicon-carbon composite is higher than that of carbon-based materials, the degree of its volume expansion or contraction during charging and discharging is relatively large, which may lead to defects such as the collapse of the structure of the negative electrode active material, bursting and powdering, and may cause undesirable side reactions inside the battery. However, since the silicon-carbon composite contains carbon element, and the carbon element can effectively alleviate the volume expansion of silicon, in this application, the upper limit of the mass content of silicon element in the silicon-carbon composite may be slightly higher than the mass content of silicon element in silicon oxide, and may reach 10%. Since too high a content may be disadvantageous to the improvement of DCR, when other conditions are met, the battery power performance corresponding to the negative electrode active material with more than 10.0% silicon-carbon composite is not as good as a battery with a lower silicon content.

[0059] In order to further improve the problem of the silicon-carbon composite being crushed and pulverized, the battery cell of the embodiment of the present application is combined with an electrolyte solution having a high content of lithium hexafluorophosphate LiPF6, and the mass content of lithium hexafluorophosphate relative to the total mass of the electrolyte solution is 15% or more.

[0060] The electrolyte with a relatively high content of lithium hexafluorophosphate LiPF6 can effectively alleviate the problem of the silicon-carbon composite bursting and powdering. Possible causes: lithium hexafluorophosphate is involved in the formation of the solid electrolyte interphase (SEI) film components on the surface of the negative electrode active material. Lithium hexafluorophosphate with a high fluorine atom ratio can optimize the SEI film components, and lithium hexafluorophosphate with a high mass content has a more significant improvement effect on the SEI film components, improving the proportion of fluorine lithium ions (e.g., lithium fluoride) in the SEI film. Such an SEI film with a relatively high proportion of fluorine lithium ions can alleviate the problem of the silicon-carbon composite bursting and powdering, and improve the structural stability of the entire negative electrode active material, while delaying the side reaction between the electrolyte and the surface of the negative electrode active material, thereby improving the discharge stability of the silicon-carbon composite in the later stage of discharge, and further improving the power performance of the battery.

[0061] In addition, at the end of discharge when the battery cell has a low SOC, the lithium ion concentration in the negative active material is relatively low, and it is relatively difficult for the lithium ions to separate from the negative active material, which reduces the lithium salt concentration difference in the electrolyte system, improves the internal resistance of the battery cell, and further reduces the discharge power. Meanwhile, the electrolyte in the embodiment of the present application contains a high content of lithium hexafluorophosphate, which contributes more lithium ions to the battery system, increases the lithium ion concentration in the electrolyte, effectively reduces the concentration polarization of the lithium salt, and promotes the migration of lithium ions from the negative electrode plate to the positive electrode plate, thereby further improving the power performance of the battery cell.

[0062] However, if the mass content of lithium hexafluorophosphate in the electrolyte is greater than 20%, the viscosity of the electrolyte will be significantly increased, which is unfavorable for the migration of lithium ions from the inside of the bulk of the negative electrode active material to the surface, and the migration rate of lithium ions from the negative electrode surface to the positive electrode surface will be slowed down, which is unfavorable for the migration of lithium ions from the surface of the negative electrode active material into the bulk of the negative electrode active material. Therefore, even if the negative electrode active material contains a silicon material with a relatively high lithium absorption / release voltage plateau, without a suitable electrolyte system, the internal resistance at the end of discharge of the battery will be increased, which is unfavorable for the discharge power performance.

[0063] To summarize the above, in the battery cell of the embodiment of the present application, the mass content of lithium hexafluorophosphate in the electrolyte is 15% to 20%, and by combining this with 0.3% to 10.0% of silicon element in the negative electrode active material, the synergistic effect between the electrolyte and the negative electrode is utilized to improve the power performance at the end of battery discharge.

[0064] For example, the mass content of silicon element in the silicon-carbon composite relative to the total mass of the negative electrode active material is 0.3% to 10.0%, and optionally 4.0% to 7.0%. For example, the range is 0.3%, 0.4%, 0.5%, 0.6%, 0.64%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.27%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 1.91%, 2.0%, 2.1%, 2.2%, 2.23%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.86%, 2.9%, 3%, 3.1%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, or a range consisting of any two of the above numbers.

[0065] In some embodiments, the mass content of silicon element in the silicon-carbon composite with respect to the total mass of the anode active material is 4.0% or more and 7.0% or less. By setting the mass content of the silicon-carbon composite within the above range, the energy density of the battery cell can be further increased, and the carbon element in the silicon-carbon composite can play a role in mitigating the expansion of the silicon element. Therefore, the expansion of the silicon-carbon composite will not become excessive. By combining with the above electrolyte system, the internal resistance at the end of discharge of the battery can be significantly reduced, and the discharge power performance can be improved.

[0066] Exemplarily, the mass content of lithium hexafluorophosphate in the electrolyte with respect to the total mass of the electrolyte may be 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 17.8%, 18%, 18.2%, 18.5%, 19%, 19.5%, 20% or a range consisting of any two of the above numerical values. Correspondingly, the mass content of the silicon-carbon composite in the anode active material to be combined is 0.5% - 10%.

[0067] As described above, the silicon element may be derived from the silicon-carbon composite. Here, the silicon-carbon composite may refer to the existence form of the silicon element in the anode plate in the battery after formation. The silicon-carbon composite may be a silicon-carbon composite formed by silicon element and carbon element through several chemical reactions in the battery cell. The silicon-carbon composite may also be formed by physically mixing silicon monomer and carbon monomer. For example, the carbon monomer includes a porous skeleton, and the silicon monomer may be located in the holes of the porous skeleton or on the surface of the porous skeleton. The silicon-carbon composite may be one with a carbon layer or the like coated on the surface of the silicon monomer.

[0068] In some embodiments, the anode active material may further contain other active materials containing silicon element. For example, the silicon element exists in the anode film layer in at least one form of silicon monomer, silicon oxide SiO x (0 < x ≤ 2). Here, the silicon monomer, the silicon-carbon composite, and the silicon oxide SiOx (0 < x ≤ 2) may refer to a silicone-based material or may refer to the form of silicon element in the negative electrode plate of the battery after formation. Here, silicon oxide SiO x , 0 < x ≤ 2 because the bonding mode between silicon atoms and oxygen atoms in the negative electrode film layer is diverse, and it may be at least one of SiO, SiO 1.2 , or SiO2 and other possible silicon oxides.

[0069] The carbon element is mainly a constituent element of the carbon-based material. In some embodiments, the carbon-based material may include at least one of artificial graphite and natural graphite.

[0070] Optionally, the carbon-based material may include artificial graphite. The combination of artificial graphite and the above electrolyte system, and the combination with the silicon-carbon composite can reduce DCR and improve power.

[0071] In some embodiments, based on the total mass of the negative electrode active material, the ratio of the mass content of the silicon-carbon composite to the mass content of the artificial graphite is (0.4:99.6) - (14.5:85.5).

[0072] When the content ratio of the silicon-carbon composite and artificial graphite in the negative electrode active material meets the requirements, the discharge power of the battery at low SOC can be further improved.

[0073] Exemplarily, the ratio of the mass content of the silicon-carbon composite to the mass content of the artificial graphite may be 0.4:99.6, 0.5:99.5, 1:99, 1.5:98.5, 2:98, 2.5:97.5, 3:97, 3.5:96.5, 4:96, 4.5:95.5, 5:95, 6.5:93.5, 7:93, 7.5:92.5, 8:92, 8.5:91.5, 9:91, 9.5:90.5, 10:90, 11:89, 12:88, 13:87, 14:86, 14.5:85.5 or a range consisting of any two of the above numerical values.

[0074] In some embodiments, the mass content of the silicon-carbon composite is 0.4% to 14.5%, and optionally 5.75% to 10%, such as 0.4%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 5.5%, 5.75%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 14.5%, or a range consisting of any two of the above values. When the mass content of the silicon-carbon composite satisfies the above content range, the cycle performance of the battery can be improved.

[0075] In some embodiments, the mass content of the synthetic graphite may be between 85.5% and 99.6%, and optionally between 90% and 94.25%, such as 85.5%, 90%, 91%, 92%, 93%, 94%, 95%, 95.1%, 95.2%, 95.3%, 95.4%, 95.5%, 95.6%, 95.7%, 95.8%, 95.9%, 96%, 96.1%, 96.2%, 96.3%, 96.4%, 96.5%. , 96.6%, 96.7%, 96.8%, 96.9%, 97%, 97.1%, 97.2%, 97.3%, 97.4%, 97.5%, 97.6%, 97.7%, 97.8%, 97.9%, 98%, 98.1%, 98.2%, 98.3%, 98.4%, 98.5%, 98.6%, 98.7%, 98.8%, 98.9%, 99%, 99.5%, 99.6%, or a range consisting of any two of the above values. When the mass content of the artificial graphite satisfies the above content range, the cycle performance of the battery can be improved.

[0076] Optionally, the carbon-based material may include natural graphite, which generally has a smaller particle size and can absorb and release lithium ions faster, and the surface of natural graphite generally contains amorphous carbon, and the presence of amorphous carbon can reduce the DCR and improve power.

[0077] The qualitative and quantitative analysis of each substance or element in this application can be detected using appropriate instruments and methods known to those skilled in the art. Relevant detection methods can refer to domestic and foreign detection standards, domestic and foreign enterprise standards, etc. And those skilled in the art can adaptively change some detection steps / instrument parameters from the perspective of detection accuracy to obtain more accurate detection results. It is possible to perform qualitative or quantitative measurement using one detection method, or to perform qualitative or quantitative measurement by combining multiple detection methods.

[0078] For example, taking the detection of silicon element in the negative electrode active material as an example, qualitative and quantitative analysis can be carried out with reference to JY / T015-1996 "General Rules for Inductively Coupled Plasma Atomic Emission Spectrometry", and further referring to the GB-T17359-2012 standard, analysis can also be carried out on the surface elements of the negative electrode plate or the cross-sectional elements after ion polishing.

[0079] For example, the graphite material in this application can be qualitatively analyzed by performing an X-ray powder diffraction test on the negative electrode plate or the negative electrode active material in combination with JIS / K0131-1996 General Rules for X-ray Diffraction Analysis. The silicon-carbon composite and silicon oxide SiO x (0 < x ≤ 2) in this application can also be tested and qualitatively analyzed using the above X-ray powder diffraction.

[0080] In some embodiments, based on the total mass of the negative electrode film layer, the mass content of the negative electrode active material is 85% or more and less than 100%. For example, the mass content of the negative electrode active material may be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or a range consisting of any two of the above numerical values.

[0081] In some embodiments, the thickness of the single-sided negative electrode film layer is 65 μm to 90 μm. The thickness of the negative electrode film layer is the thickness of the single-sided negative electrode film layer, and for example, when a negative electrode film layer is provided on both sides of the negative electrode current collector, the thickness of the negative electrode film layer on one side of the negative electrode current collector is the thickness of one side of the negative electrode film layer, or when a negative electrode film layer is provided on one side of the both sides of the negative electrode current collector, the thickness of the negative electrode film layer on this side is the thickness of the single-sided negative electrode film layer. When the thickness of the negative electrode film layer is in the above range, the transmission rate of lithium ions in the negative electrode plate and the transmission rate in the separator can be basically matched, and the risk of deterioration of concentration polarization can be reduced, which is advantageous for improving discharge performance.

[0082] For example, the thickness of the negative electrode film layer may be 65 μm, 66 μm, 67 μm, 68 μm, 69 μm, 70 μm, 71 μm, 72 μm, 73 μm, 74 μm, 75 μm, 76 μm, 77 μm, 78 μm, 79 μm, 80 μm, 81 μm, 82 μm, 83 μm, 84 μm, 85 μm, 86 μm, 87 μm, 88 μm, 89 μm, 90 μm, or a range consisting of any two of the above numerical values.

[0083] In the embodiment of the present application, the thickness of the negative electrode film layer is a known meaning in the art, and can be detected by using instruments and methods known in the art. The relevant detection method can be referred to domestic and foreign detection standards, domestic and foreign enterprise standards, etc., and those skilled in the art can adaptively change some detection steps / instrument parameters, etc., from the viewpoint of detection accuracy to obtain more accurate detection results. One detection method can be used to perform qualitative or quantitative measurement, or multiple detection methods can be used in combination to perform qualitative or quantitative measurement. For example, according to GB / T 17359-2012 "Quantitative Analysis by Microbeam Analysis Spectroscopy", a negative electrode plate containing no electrolyte is used as a sample to perform ion polishing cross-sectional elemental analysis to obtain the thickness of the negative electrode film layer. For example, measurements are taken multiple times with a micrometer and the average value is taken: take a negative electrode plate that does not contain electrolyte (a negative electrode plate with a negative electrode film layer applied on both sides), first test the thickness of any five parts of the negative electrode plate with a micrometer to obtain an average value H1, wipe off the negative electrode film layer, and then test the thickness of any five parts of the remaining current collector to obtain an average value H2. The thickness of a single layer of negative electrode film layer is (H2-H1) / 2.

[0084] In some embodiments, the packed density PD of the negative electrode membrane layer is 1.3 g / cm 3 ~1.7g / cm 3 When the packing density of the negative electrode film layer is within this range, the negative electrode plate has good dynamic performance and cycle performance.

[0085] Exemplarily, the compaction density PD of the negative electrode film layer is 1.3 g / cm 3 , 1.35g / cm 3 , 1.4g / cm 3 , 1.45g / cm 3 , 1.5g / cm 3 , 1.55g / cm 3 , 1.6g / cm 3 , 1.65g / cm 3 , 1.7g / cm 3 Or, it may be a range consisting of any two of the above values.

[0086] Areal density = weight of negative electrode film layer on one side / area of ​​negative electrode film layer on one side, and since there is a negative electrode film layer on both sides of the negative electrode current collector, the weight of negative electrode film layer on one side = (average weight of plate - average weight of current collector) / 2. Compaction density = areal density / average thickness of negative electrode film layer, and since there is a negative electrode film layer on both sides of the negative electrode current collector, the average thickness of negative electrode film layer = (average thickness of plate - average thickness of current collector) / 2.

[0087] The "average" here may be the average value after five parallel tests.

[0088] In some embodiments, the negative electrode film layer further optionally includes a negative electrode conductive agent. The embodiments of the present application are not particularly limited to the type of the negative electrode conductive agent, and for example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, based on the total mass of the negative electrode film layer, the mass content of the negative electrode conductive agent is ≦5%.

[0089] In some embodiments, the negative electrode film layer further optionally includes a negative electrode adhesive. The embodiments of the present application are not particularly limited to the type of the negative electrode adhesive, and for example, the negative electrode adhesive may include styrene butadiene rubber SBR, water-soluble unsaturated resin SR-1B, water-soluble acrylic acid-based resin (e.g., at least one of polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS, polyacrylamide PAM, polyvinyl alcohol PVA, sodium alginate SA, and carboxymethyl chitosan CMCS). In some embodiments, based on the total mass of the negative electrode film layer, the mass content of the negative electrode adhesive is ≦5%.

[0090] In some embodiments, the negative electrode membrane layer further optionally includes other auxiliary agents. For example, the other auxiliary agents may include thickeners, such as sodium carboxymethylcellulose CMC-Na, PTC thermistor materials, etc. In some embodiments, based on the total mass of the negative electrode membrane layer, the mass content of the other auxiliary agents is ≦2%.

[0091] In some embodiments, the negative electrode current collector may be a metal foil sheet or a composite current collector. An example of the metal foil sheet may be copper foil. The composite current collector may include a polymer base layer and a metal material layer formed on at least one surface of the polymer base layer. For example, the metal material in the metal material layer may include at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. For example, the polymer base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0092] In some embodiments, the thickness of the negative electrode current collector is 6 μm or less, and optionally is a thin current collector of 4.5 μm to 6 μm, for example a thin metal current collector.

[0093] The negative electrode current collector of the battery cell of the present application is optionally a thin current collector of 4.5 μm to 6 μm, which can weaken the heat dissipation path of the battery cell and reserve some heat within the battery under low SOC discharge conditions, and further increase the beneficial effect of reducing DCR growth at the end of discharge (low SOC) by combining the low silicon negative electrode plate with a high content lithium hexafluorophosphate electrolyte system, thereby improving the discharge power at low SOC.

[0094] For example, the thickness of the negative electrode current collector may be 4.0 μm, 4.1 μm, 4.2 μm, 4.3 μm, 4.4 μm, 4.5 μm, 4.6 μm, 4.7 μm, 4.8 μm, 4.9 μm, 5.0 μm, 5.1 μm, 5.2 μm, 5.3 μm, 5.4 μm, 5.5 μm, 5.6 μm, 5.7 μm, 5.8 μm, 5.9 μm, 6 μm, or a range consisting of any two of the above numerical values.

[0095] The negative electrode film layer is generally obtained by applying a negative electrode slurry onto a negative electrode current collector, drying, and cold pressing. The negative electrode slurry is generally formed by dispersing a negative electrode active material, an optional conductive agent, an optional adhesive, and other optional auxiliary agents in a solvent and uniformly stirring the mixture. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.

[0096] The negative electrode plate does not exclude additional functional layers other than the negative electrode film layer. For example, in some examples, the negative electrode plate of the embodiment of the present application further includes a conductive undercoating (e.g., made of a conductive agent and an adhesive) sandwiched between the negative electrode collector and the negative electrode film layer and disposed on the surface of the negative electrode collector. In some examples, the negative electrode plate of the embodiment of the present application further includes a protective layer covering the surface of the negative electrode film layer.

[0097] In some embodiments, the electrolyte further comprises an organic solvent.

[0098] In some embodiments, the organic solvent may include a cyclic carbonate, and the ratio of the mass content of the cyclic carbonate to the mass content of the lithium hexafluorophosphate, based on the total mass of the electrolyte, is (0.60-2.50):1, optionally (1.00-1.65):1.

[0099] The presumable beneficial effects are as follows: when the ratio of the mass content of the cyclic carbonate to the mass content of lithium hexafluorophosphate is within the above range, it is advantageous for sufficiently dissociating more lithium ions from lithium hexafluorophosphate, so that even at the end of discharge with a low SOC, more lithium ions can be contained in the electrolyte system, and the lithium ions can be continuously dissociated as the battery reaction proceeds, thereby improving the power performance of the battery.

[0100] Exemplarily, the ratio of the mass content of the cyclic carbonate to the mass content of the lithium hexafluorophosphate may be 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.15:1, 1.2:1, 1.3:1, 1.35:1, 1.37:1, 1.4:1, 1.5:1, 1.6:1, 1.65:1, 1.67:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1, or a range consisting of any two of the above values.

[0101] In some embodiments, the mass content of the cyclic carbonate in the electrolyte is 10% to 45%, and more preferably 20% to 30%. The cyclic carbonate has a high dielectric constant and a high ionic conductivity, and can form a stable SEI film on the surface of the negative electrode active material, which is advantageous for the power performance of the battery at the end of discharge.

[0102] Exemplarily, the mass content of the cyclic carbonate may be 10%, 10.92%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 20.93%, 21%, 22%, 23%, 23.66%, 24%, 25%, 26%, 27%, 28%, 29%, 29.12%, 30%, 30.03%, 31%, 32%, 33%, 34%, 35%, 36%, 36.4%, 37%, 38%, 39%, 40%, 40.4%, 41%, 42%, 43%, 44%, 45%, or a range consisting of any two of the above values.

[0103] In some embodiments, the cyclic carbonate may include at least one of ethylene carbonate EC, propylene carbonate PC, and butylene carbonate BC.

[0104] In some embodiments, the organic solvent may include a chain carbonate, and the ratio of the mass content of the chain carbonate to the mass content of the cyclic carbonate based on the total mass of the electrolyte is (0.9-6):1, and optionally (1.5-2.65):1. When the mass content ratio of the chain carbonate to the cyclic carbonate satisfies the above range, the viscosity and ionic conductivity of the electrolyte can be improved at the same time, and the kinetic performance of the lithium ion can be improved.

[0105] Exemplary ratios of the mass content of the linear carbonate to the mass content of the cyclic carbonate are 0.9:1, 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.37:1, 1.4:1, 1.5:1, 1.6:1, 1.65:1, 1.67:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3.0:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9 ... :1, 3.3:1, 3.4:1, 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9:1, 4.0:1, 4.1:1, 4.2:1, 4.3:1, 4.4:1, 4.5:1, 4.6:1, 4.7:1, 4.8:1, 4.9:1, 5.0:1, 5.1:1, 5.2:1, 5.3:1, 5.4:1, 5.5:1, 5.6:1, 5.7:1, 5.8:1, 5.9:1, 5.95:1, 6:1, or a range consisting of any two of the above numerical values.

[0106] In some embodiments, the mass content of the chain carbonate is 35% to 65%, and more preferably 50% to 60%. The chain carbonate has a relatively low viscosity, which contributes to sufficient dissolution of lithium hexafluorophosphate with a high content, and is advantageous for lithium ions ionized from lithium hexafluorophosphate to rapidly move between the positive and negative electrodes. The combined use of the chain carbonate and the cyclic carbonate also contributes to increasing the electrochemical stability of the electrolyte system and effectively reducing side reactions of the electrolyte.

[0107] For example, the mass content of the chain carbonate may be 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 50.4%, 51%, 52%, 52.5%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, or a range consisting of any two of the above values.

[0108] In some embodiments, the linear carbonate comprises at least one of ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dimethyl carbonate (DMC).

[0109] In some embodiments, the electrolyte may further include an additive.

[0110] In some embodiments, the additive may include a fluorinated cyclic carbonate.

[0111] In some embodiments, the fluorinated cyclic carbonate includes at least one of monofluoroethylene carbonate (FEC), bisfluoroethylene carbonate (DFEC), and trifluoropropylene carbonate (TFPC), and optionally, the fluorinated cyclic carbonate includes monofluoroethylene carbonate (FEC). FEC contains a relatively small number of fluorine atoms, has a stronger polarity, and is more likely to be released and participate in the film-forming reaction of the SEI film.

[0112] In some embodiments, the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of elemental silicon relative to the total mass of the electrolyte is (0.01-9.5):1, and optionally (0.01-0.15):1.

[0113] Illustratively, the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of the silicon element relative to the total mass of the electrolyte may be 0.01:1, 0.02:1, 0.03:1, 0.035:1, 0.04:1, 0.05:1, 0.055:1, 0.06:1, 0.07:1, 0.08:1, 0.1:1, 0.15:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.05:1, 1.1:1, 1.2:1, 1.3:1, 1.35:1, 1.4:1, 1. The ratio may be 5:1, 1.57:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.36:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 4.7:1, 4.71:1, 4.8:1, 5:1, 5.5:1, 5.8:1, 6:1, 6.5:1, 7:1, 7.5:1, 7.8:1, 8:1, 8.5:1, 9:1, 9.1:1, 9.2:1, 9.3:1, 9.4:1, 9.43:1, 9.5:1, or a range consisting of any two of the above values.

[0114] Fluorinated cyclic carbonate is involved in the formation of SEI film on the surface of the negative electrode active material, and can improve the film components and properties, and can effectively protect the negative electrode active material. Especially in the case of a negative electrode containing silicon, due to the characteristics of silicon expansion, it is necessary to further optimize the film composition of the SEI film formation. The optimization of the film composition is adjusted by adjusting the relative proportion of the film-forming additive in the electrolyte. The film formed by the participation of fluorinated cyclic carbonate can improve the flexibility of the SEI film, and can improve the collapse of the structure caused by the release of a large amount of lithium ions in a short time at the end of discharge. Fluorinated cyclic carbonate has a certain desolvation ability, which is favorable for the migration of lithium ions, and can improve the DCR at low SOC and increase the discharge power. As a result of the research, it was found that when the ratio of the silicon content in the negative electrode active material to the FEC content in the electrolyte satisfies (0.01 to 9.5): 1, the power supply performance of the battery at the end of discharge is obviously improved. Since the carbon element in the silicon-carbon composite can effectively mitigate the volume change of the silicon element, the fluorinated cyclic carbonate with a relatively low content can also significantly improve the discharge power performance of the battery cell, and optionally, the ratio of the silicon content in the negative electrode active material to the FEC content in the electrolyte satisfies (0.01-0.15):1.

[0115] In some embodiments, the mass content of the fluorinated cyclic carbonate relative to the total mass of the electrolyte may be 0.05% to 5.8%, and optionally 0.1% to 1.0%.

[0116] For example, the mass content of fluorinated cyclic carbonate relative to the total mass of the electrolyte is 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 0.95%, 0.98%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, and 1.8%. The range may be 8%, 1.9%, 1.91%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.82%, 3.9%, 4%, 4.1%, 4.5%, 5%, 5.2%, 5.5%, 5.7%, 5.73%, 5.8%, or a range consisting of any two of the above numbers.

[0117] In some embodiments, the additive may further include at least one of 1,3-propane sultone PS, vinylene carbonate VC, and lithium fluorosulfonate LiSO3F.

[0118] In some embodiments, the ratio of the mass content of 1,3-propane sultone PS, the mass content of vinylene carbonate VC, and the mass content of lithium fluorosulfonate LiSO3F based on the total mass of the electrolyte is (0.050-0.300):(0.100-0.500):(0.001-0.300). When the ratio of the mass content of 1,3-propane sultone PS, the mass content of vinylene carbonate VC, and the mass content of lithium fluorosulfonate LiSO3F is within the above range, the above components can essentially participate in the formation of an SEI film on the surface of the negative electrode active material, and the SEI film can effectively mitigate the expansion of the silicon-carbon composite.

[0119] In some embodiments, the mass content of 1,3-propane sultone PS is 0.1% to 1%, for example 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, or a range consisting of any two of the foregoing values.

[0120] In some embodiments, the mass content of vinylene carbonate VC is 0.1% to 1%, for example 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, or a range consisting of any two of the foregoing values.

[0121] In some embodiments, the mass content of lithium fluorosulfonate LiSO3F is between 0.1% and 1%, such as 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, or a range consisting of any two of the foregoing values.

[0122] After being dissolved in an organic solvent, lithium salts can release a large amount of active lithium ions and participate in charging and discharging. Some lithium salts can also optimize the structure of the SEI film, improve the electrolyte reaction activity, reduce side reactions, and even improve the discharge power of the battery.

[0123] In some embodiments, the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of the lithium salt, based on the total mass of the electrolyte, is (0.005-0.30):1, and optionally (0.005-0.03):1.

[0124] The fluorinated cyclic carbonate forms an organic substance on the surface of the silicon-carbon composite and can improve the flexibility of the SEI film. The lithium salt is involved in the formation of the SEI film and can include an inorganic component in the SEI film, which is advantageous for increasing the ionic conductivity and electronic conductivity performance of the SEI film and can improve the ionic conductivity and electronic conductivity performance of the entire negative electrode plate. When the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of the lithium salt is within the above range, not only can the flexibility, ionic conductivity, and electronic conductivity performance of the SEI film be improved, but the discharge power of the battery can also be increased by reducing the DCR.

[0125] Illustratively, the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of the lithium salt may be 0.005:1, 0.006:1, 0.007:1, 0.008:1, 0.009:1, 0.010:1, 0.012:1, 0.014:1, 0.016:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0. The ratio may be 10:1, 0.11:1, 0.12:1, 0.13:1, 0.14:1, 0.15:1, 0.16:1, 0.17:1, 0.18:1, 0.19:1, 0.20:1, 0.21:1, 0.22:1, 0.23:1, 0.24:1, 0.25:1, 0.26:1, 0.27:1, 0.28:1, 0.29:1, 0.30:1, or a range consisting of any two of the above values.

[0126] In some embodiments, the lithium salt further comprises at least one of a fluorine-containing inorganic phosphate and a fluorine-containing inorganic borate, which can participate in the formation of inorganic components in the SEI film, which is beneficial for enhancing the ionic and electronic conductivity performance of the SEI film, and the interfacial ionic impedance of the formed SEI film is relatively low, which is beneficial for the transmission of lithium ions, and can improve the DCR at low SOC.

[0127] In some embodiments, the fluorine-containing inorganic phosphate comprises at least one of lithium monofluorophosphate Li2PO3F and lithium difluorophosphate LiPO2F2, and optionally, the fluorine-containing inorganic phosphate comprises lithium difluorophosphate LiPO2F2.

[0128] In some embodiments, the fluorine-containing inorganic borate comprises at least one of lithium tetrafluoroborate LiBF4 and lithium difluoro(oxalato)borate LiDFOB, and optionally, the fluorine-containing inorganic borate comprises lithium tetrafluoroborate LiBF4.

[0129] In some embodiments, based on the total mass of the electrolyte, the mass content of the fluorine-containing inorganic phosphate or fluorine-containing inorganic borate is 0.05% to 0.50%, optionally 0.10% to 0.30%.

[0130] For example, the mass content of the fluorine-containing inorganic phosphate or fluorine-containing inorganic borate may be 0.05%, 0.06%, 0.08%, 0.1%, 0.15%, 0.18%, 0.2%, 0.22%, 0.25%, 0.28%, 0.3%, 0.32%, 0.35%, 0.38%, 0.4%, 0.42%, 0.45%, 0.48%, 0.5%, or a range consisting of any two of the above values.

[0131] Exemplary lithium salts include lithium difluorophosphate LiPO2F2 and lithium tetrafluoroborate LiBF4.

[0132] Alternatively, based on the total mass of the electrolyte, the mass content of lithium difluorophosphate LiPO2F2 may be 0.05% to 0.5%, and alternatively 0.10% to 0.30%, for example, the mass content of lithium difluorophosphate LiPO2F2 may be 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, or a range consisting of any two of the above values.

[0133] Alternatively, based on the total mass of the electrolyte, the mass content of lithium tetrafluoroborate LiBF4 may be 0.1% to 0.3%, for example, the mass content of lithium tetrafluoroborate LiBF4 may be 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, or a range consisting of any two of the above values.

[0134] Alternatively, based on the total mass of the electrolyte, the mass content of lithium difluoro(oxalato)borate LiDFOB may be 0.01% to 0.1%, for example, 0.01%, 0.02%, 0.05%, 0.08%, 0.1%, or a range consisting of any two of the above values.

[0135] The qualitative and quantitative determination of each substance or element in the present application can be detected using appropriate instruments and methods known to those skilled in the art, and the relevant detection methods can be referred to domestic and foreign detection standards, domestic and foreign corporate standards, etc., and those skilled in the art can adaptively change some detection steps / instrument parameters, etc. from the viewpoint of detection accuracy to obtain more accurate detection results. One detection method can be used for qualitative or quantitative measurement, or multiple detection methods can be used in combination for qualitative or quantitative measurement.

[0136] In the embodiment of the present application, the type and content of inorganic components / lithium salts in the electrolyte are known in the art and can be detected using instruments and methods known in the art, for example, the inorganic components / lithium salts in the electrolyte can be qualitatively or quantitatively analyzed by ion chromatography analysis with reference to the standard JY / T020-1996 "General Rules for Ion Chromatography Analysis Method". In the embodiment of the present application, a newly manufactured electrolyte can be taken as a sample, or a battery that has already been discharged (discharged to the lower cutoff voltage to make the battery's charge state about 0% SOC) can be reverse disassembled, and the released electrolyte obtained from the battery can be used as a sample for detection using ion chromatography analysis.

[0137] In the embodiment of the present application, the type and content of organic components in the electrolyte are the meanings known in the art, and can be detected using the instruments and methods known in the art, for example, the organic components in the electrolyte can be qualitatively and quantitatively analyzed by gas chromatography with reference to GB / T9722-2006 "General Rules for Gas Chromatography Method of Chemical Reagents". In the embodiment of the present application, a newly manufactured electrolyte can be taken as a sample, or a battery that has already been discharged (discharged to the lower cutoff voltage to make the battery's charge state about 0% SOC) can be reversely disassembled, and the free electrolyte obtained from the battery can be used as a sample for detection using ion chromatography analysis.

[0138] For example, in order to test the components of an additive in an electrolyte by liquid nuclear magnetic chromatography (NMR) to detect lithium difluorophosphate and lithium hexafluorophosphate, a 7 ml glass bottle is prepared in a nitrogen gas glove box, 5 ml of nuclear magnetic reagent premix liquid is added to the glass bottle, and the bottle is left in a nitrogen gas glove box at room temperature of 20-25°C for 24 hours to allow the electrolyte in the plate and separator to diffuse into the nuclear magnetic reagent premix liquid, thereby obtaining a nuclear magnetic test sample. The nuclear magnetic premix liquid includes 100 ml of deuterated acetonitrile and 3 ml of trifluoromethylbenzene C7H5F3, and the above nuclear magnetic reagent premix liquid is pre-dried with molecular sieve 4A in advance (15 g of unlocked 4A molecular sieve is added to 100 ml of nuclear magnetic reagent premix liquid, and dried for 30 days in a nitrogen gas glove box at room temperature of 20-25°C). Measurements are performed using 19F NMR (nuclear magnetic resonance (NMR): Bruker Avance 400HD).

[0139] In order to identify and quantify each species, the following settings for inversion angle and scan time are adopted:

[0140] Fluorine spectrum test pulse sequence: 2gfhigqn.2, Extension time: 1 second, Number of scans: 16.

[0141] The relative contents of trifluoromethylbenzene and LiPF6 were calculated based on the signal peak integral intensity of both substances in F-NMR. The calculation method is: PF6 - Relative content = (I PF6 - ×M PF6 - / 6) / (I CF3ph ×M CF3ph / 3), where I is the corresponding nuclear magnetic peak area, M is the corresponding relative molecular weight, and the content of lithium hexafluorophosphate in the electrolyte is calculated based on the molar ratio relationship between hexafluorophosphate radicals and lithium ions.

[0142] Trifluoromethylbenzene and PO2F2 in F-NMR - Calculate the relative content of both substances based on the integrated intensity of the signal peaks of both substances. The calculation method is: PO2F2 - Relative content = (I PO2F2- ×M PO2F2- / 2) / (I CF3ph ×M CF3ph / 3), where I is the corresponding nuclear magnetic peak area, M is the corresponding relative molecular weight, and calculate the content of lithium difluorophosphate in the electrolyte based on the molar ratio relationship between difluorophosphate radicals and lithium ions.

[0143] In some embodiments, the various solutes or solvents in the electrolyte solutions referred to in this application include substances that are added spontaneously when the electrolyte solution is manufactured, and also include substances derived from substances already present in / some electrolyte solutions during the manufacture of the electrolyte solution or during the manufacture of a battery with said electrolyte solution or during storage or use of a battery containing said electrolyte solution.

[0144] In some embodiments, the battery cell has a retention coefficient between 1.0 g / Ah and 2.5 g / Ah, optionally between 1.0 g / Ah and 1.5 g / Ah.

[0145] The liquid retention coefficient of a battery cell can reflect the liquid retention capacity of the electrolyte. When the liquid retention coefficient of a battery cell is within the above range, the electrolyte can have a relatively good infiltration effect on the positive electrode plate and the negative electrode plate, and there is a certain gap between the negative electrode plate and the separator, which provides an expansion space for the volume expansion of the silicon-carbon composite, and reduces the risk of the entire battery swelling.

[0146] For example, the electrolyte retention coefficient of the battery may be 1.0 g / Ah, 1.1 g / Ah, 1.2 g / Ah, 1.3 g / Ah, 1.4 g / Ah, 1.5 g / Ah, 1.6 g / Ah, 1.7 g / Ah, 1.8 g / Ah, 1.9 g / Ah, 2.0 g / Ah, 2.1 g / Ah, 2.2 g / Ah, 2.3 g / Ah, 2.4 g / Ah, 2.5 g / Ah, or a range consisting of any two of the above values.

[0147] In the embodiment of the present application, the electrolyte retention coefficient of the battery cell has a meaning known in the art and can be detected by using instruments and methods known in the art, for example, according to GB / T 31486-2015 "Electrical performance requirements and test methods for power storage batteries for electric vehicles", at 25°C, a lithium ion battery is charged at 1C to 4.35V, and then discharged at 1C to 2.8V, the resulting discharge capacity C is taken as the denominator, the lithium ion battery is weighed as M0, and the positive electrode plate, the negative electrode plate, the separator and the electrolyte are disassembled, where the released electrolyte is stored in a housing / bag, and all the above solid assemblies are placed in an oven at 60°C for baking for more than 4 hours (including but not limited to the positive electrode plate, the negative electrode plate, the separator, and further including other mechanical parts that contribute to the M0 of the disassembled battery cell), and the entire assembly of the battery cell is weighed as M1, where the weight difference between M0 and M1 is taken as the numerator. The liquid retention coefficient is equal to the volume C divided by the weight difference between M0 and M1.

[0148] In some embodiments, the battery cell may further include a separator, the porosity of the separator being between 30% and 40%.

[0149] In the battery cell of the present application, the additive amount of lithium hexafluorophosphate is relatively high, and therefore the viscosity of the entire electrolyte is relatively high, and the porosity of the separator is relatively high, which is advantageous for the electrolyte with a relatively high viscosity to pass through the separator, allowing smooth movement of lithium ions.

[0150] Exemplarily, the porosity of the separator may be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, or a range consisting of any two of the above values.

[0151] In the embodiment of the present application, the porosity is the percentage of the volume of the holes in the separator to the total volume of the separator. The porosity can be tested according to the standard GB / T 36363-2018 "Polyolefin Separator for Lithium-Ion Batteries".

[0152] In some embodiments, the separator includes an organic substrate and a coating disposed on at least one side of the organic substrate, the coating including a heat-resistant layer and an organic layer, the heat-resistant layer being located on a surface of the organic substrate and the organic layer being disposed on a surface of the heat-resistant layer facing away from the organic substrate. The separator in combination with the electrolyte and the negative electrode plate can significantly improve the power performance of the battery cell.

[0153] Optionally, the heat-resistant layer includes inorganic particles.The combination of the separator with the electrolyte and the negative electrode plate can significantly improve the power performance of the battery cell.

[0154] Optionally, the organic layer comprises one of a non-fluorinated polymer and a fluorine-containing polymer, and optionally, the organic layer comprises a non-fluorinated polymer, for example, the non-fluorinated polymer comprises a polyacrylate, in which case the organic layer is a polyacrylate layer. Combining the separator with the electrolyte and the negative electrode plate can significantly improve the power performance of the battery cell.

[0155] Exemplarily, the coating may include a ceramic layer and / or a polyacrylate layer, the coating may include only a ceramic layer, or only a polyacrylate layer, or the coating may include a ceramic layer and a polyacrylate layer.

[0156] Alternatively, when the coating comprises a ceramic layer and a polyacrylate layer, the polyacrylate layer may be disposed on at least one surface of the organic substrate and the ceramic layer may be disposed on a surface of the polyacrylate layer facing away from the organic substrate, or the ceramic layer may be disposed on at least one surface of the organic substrate and the polyacrylate layer may be disposed on a surface of the ceramic layer facing away from the organic substrate.

[0157] By installing a polyacrylate layer on the outer surface of the separator, the outer surface of the separator has a certain flexibility, which can effectively mitigate the volume expansion or contraction of the silicon-carbon composite, and improve the structural stability of the entire electrode assembly.

[0158] There is no particular limitation on the material of the organic substrate, and any known base film having good chemical stability and mechanical stability can be selected, for example, the organic substrate includes at least one of a porous polyolefin resin film (e.g., at least one of polyethylene, polypropylene, polytetrafluoroethylene, polyvinyl fluoride, and polyvinylidene fluoride), a porous glass fiber, and a porous nonwoven fabric. The organic substrate may be selected from a single layer film or a multilayer composite film. When the organic substrate is a multilayer composite film, the materials of each layer may be the same or different.

[0159] In some embodiments, the organic substrate has a thickness between 6.6 μm and 7.6 μm.

[0160] When the thickness of the organic base material is within the above range, the lithium ion transmission rate in the negative electrode plate and the transmission rate in the separator can be basically matched, reducing the risk of deterioration of concentration polarization, which is advantageous for improving discharge performance.

[0161] Exemplarily, the thickness of the organic substrate may be 6.6 μm, 6.7 μm, 6.8 μm, 6.9 μm, 7.0 μm, 7.1 μm, 7.2 μm, 7.3 μm, 7.4 μm, 7.5 μm, 7.6 μm, or a range consisting of any two of the above values.

[0162] In some embodiments, the polyacrylate in the polyacrylate layer may be formed by polymerization of a polymer monomer, the polymer monomer including at least one of a first polymer monomer, a second polymer monomer, and a third polymer monomer. Optionally, the polymer monomer includes a first polymer monomer, a second polymer monomer, and a third polymer monomer. By forming the polyacrylate by polymerization of the three types of polymer monomers, the separator can have suitable adhesion to the electrodes and improve the dynamic performance of the battery.

[0163] The first polymer monomer has at least one ester bond and is optionally one or more of methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, vinyl acetate, trifluoroethyl methacrylate, glycidyl methacrylate, or trimethylolpropane triacrylate, more optionally one or more of methyl methacrylate, lauryl acrylate, lauryl methacrylate, or trimethylolpropane triacrylate.

[0164] The second polymer monomer has at least one cyano bond and is optionally one or more of acrylonitrile, methacrylonitrile, ethacrylonitrile, more preferably one or more of acrylonitrile, methacrylonitrile.

[0165] The third polymer monomer has at least one amide bond and is optionally one or more of acrylamide, N-methylolacrylamide, N-butoxymethacrylamide, more preferably one or more of acrylamide, N-methylolacrylamide.

[0166] In some embodiments, the weight ratio of the first polymer monomer to the second polymer monomer to the third polymer monomer in the polyacrylate formed above is (45-70):(10-25):(10-35), for example, (50-70):(10-25):(10-35), (55-70):(10-25):(10-35), (60-70):(10-25):(10-35), (65-70):(10-25):(10-35). ), (45~70):(15~25):(10~35), (45~70):(20~25):(10~35), (45~70):(22~25):(10~35), (45~70):(10~25):(15~35), (45~70):(10~25):(20~35), (45~70):(10~25):(25~35), (45~70):(10~25):(30~35), (45~70):(10~25):(32~35), etc.

[0167] In some embodiments, the ceramic layer includes inorganic particles having heat resistance properties, which may include at least one of inorganic particles having a dielectric constant of 5 or higher, inorganic particles having active ion transport capabilities, and inorganic particles capable of generating electrochemical oxidation and reduction.

[0168] In some embodiments, the inorganic particles having a dielectric constant of 5 or higher are boehmite (γ-AlOOH), aluminum oxide (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), silicon oxide SiO x(0 < x ≤ 2), tin dioxide (SnO2), titanium dioxide (TiO2), calcium oxide (CaO), zinc oxide (ZnO), zirconium dioxide (ZrO2), yttrium oxide (Y2O3), nickel oxide (NiO), hafnium dioxide (HfO2), cerium oxide (CeO2), zirconium titanate (ZrTiO3), barium titanate (BaTiO3), magnesium fluoride (MgF2), Pb(Zr,Ti)O3 (abbreviation: PZT), Pb 1-m La m Zr 1-n Ti n O3 (abbreviation: PLZT, 0 < m < 1, 0 < n < 1) and Pb(Mg3Nb 2 / 3 )O3 - PbTiO3 (abbreviation: PMN - PT) may include at least one of them.

[0169] In some embodiments, the inorganic particles having the ability to transmit active ions are lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y - based glass (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), lithium germanium thiophosphate (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride (Li x N y , 0 < x < 4, 0 < y < 2), SiS2 - based glass (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4) and P2S5 - based glass (Li x P y S zIt may include at least one of (0 < x < 3, 0 < y < 3, 0 < z < 7).

[0170] In some embodiments, the inorganic particles capable of generating electrochemical oxidation and reduction may include at least one of lithium-containing transition metal oxides, olivine-structured lithium-containing phosphates, carbon-based materials, silicone-based materials, tin-based materials, and lithium titanium compounds.

[0171] In some embodiments, the ceramic layer may further include an adhesive. Optionally, the adhesive includes one or more of polyacrylate, acrylic acid, carboxymethyl cellulose, polyvinylidene fluoride-co-trichloroethylene copolymer, polymethyl methacrylate, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate copolymer, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, polyvinylidene fluoride, polyacrylonitrile, polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, tetrafluoroethylene, polyethylene, polypropylene, and cyanoethyl pullulan.

[0172] In some embodiments, the thickness of the coating is 1.5 μm to 2.5 μm.

[0173] The thickness of the coating is the thickness of the coating on one side. Specifically, it includes the total thickness of the ceramic layer and the polyacrylate layer. For example, when coatings are provided on both sides of the organic substrate, the thickness of the coating on one side of the organic substrate is the thickness of the coating on one side, or when a coating is provided on one side of the two sides of the organic substrate, the thickness of this side coating is the thickness of the coating on one side. When the thickness of the coating is within the above range, the transmission rate of lithium ions in the negative electrode plate and the transmission rate in the separator can be basically made to match, and the risk of concentration polarization deterioration can be reduced, which is advantageous for improving the discharge performance.

[0174] Illustratively, the coating thickness may be 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, or a range consisting of any two of the foregoing values.

[0175] In some embodiments, the ratio of the thickness of the ceramic layer to the thickness of the polyacrylate layer can be (0.5-2.0):1, e.g., 0.5:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, or a range consisting of any two of the foregoing values.

[0176] In the embodiment of the present application, the meaning of organic substrate and coating thickness is the meaning known in the art, and can be detected by using the equipment and method known in the art, for example, the combination of an ion cross section polishing apparatus and a scanning electron microscope can be used for testing. For example, the operation can be performed according to the following steps. First, the separator is cut into a sample to be measured of a certain size (for example, 6 mm x 6 mm), the sample to be measured is sandwiched between two sheets of conductive and heat conductive sheets (for example, copper foil), and the sample to be measured and the sheets are bonded and fixed with adhesive (for example, double-sided adhesive), and an iron block is pressed with a certain mass (for example, about 400 g) for a certain time (for example, 1 h) to make the gap between the sample to be measured and the copper foil as small as possible, and then the edges are aligned with scissors, and the sample is attached to a sample stand with conductive adhesive, so that the sample protrudes slightly from the edge of the sample stand. Then, the sample stage is locked and fixed on the sample shelf, the power of the argon ion cross-section polishing device is turned on, and the vacuum (e.g., 10 Pa-4 Pa), argon gas flow rate (e.g., 0.15 MPa), voltage (e.g., 8 KV) and polishing time (e.g., 2 hours) are set, the sample stage is adjusted to the oscillation mode and polishing begins, and after polishing is completed, an ion polishing cross-section topography (CP) image of the sample to be measured is obtained using a scanning electron microscope (e.g., ZEISS Sigma 300), and the thickness of the coating and the thickness of the organic substrate are measured.

[0177] In some embodiments, the battery cell further includes a positive electrode plate.

[0178] In some embodiments, the positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector and containing a positive electrode active material. For example, the positive electrode current collector has two opposing surfaces in its thickness direction, and the positive electrode film layer is disposed on either one or both of the two opposing surfaces of the positive electrode current collector.

[0179] The positive electrode film layer contains a positive electrode active material, and the positive electrode active material can employ a positive electrode active material for batteries known in the art. By way of example, the positive electrode active material may include at least one material among layered structure positive electrode active materials (such as lithium nickel cobalt manganese oxide, lithium nickel oxide / sodium, lithium cobalt oxide / sodium, lithium manganese oxide / sodium, lithium / sodium-rich layered and rock salt phase layered materials, etc.), olivine type phosphate active materials, and spinel structure positive electrode active materials (such as spinel lithium manganese oxide, spinel lithium nickel manganese oxide, lithium-rich spinel lithium manganese oxide, and lithium nickel manganese oxide, etc.).

[0180] In some embodiments, the positive electrode active material has the chemical formula Li d Ni a Co b Mn c M (1-a-b-c) Y z and contains a compound of, where 0 < d ≤ 2.1, 0.6 < a < 1, 0 < b < 1, 0 < c < 1, and 0.6 < a + b + c < 1, 1.8 ≤ z ≤ 3.5. The M element contains at least one element among B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, Ce, and the Y element contains at least one element among O, F. By combining the above positive electrode active material system with the above electrolyte and the negative electrode plate, the power performance of the battery cell can be significantly improved.

[0181] In addition to containing lithium, the positive electrode active material further contains nickel, cobalt, manganese and M elements, where the nickel can increase the gram capacity of the positive electrode active material, the cobalt can stabilize the crystal structure of the positive electrode active material, the manganese can increase the structural stability of the entire positive electrode active material, and the M element can improve the crystalline structure stability of the positive electrode active material.

[0182] In some embodiments, d is 0.01, 0.02, 0.05, 0.08, 0.10, 0.12, 0.15, 0.18, 0.20, 0.22, 0.25, 0.28, 0.30, 0.32, 0.35, 0.38, 0.40, 0.42, 0.45, 0.48, 0.50, 0.52, 0.55, 0.58, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 100, 101, 102, 103, 104, 105, 106, 107, 108, 109, 109, 108, 109, 1010, 109, 109, 109, 109, 109, 109, 109, 109, 109, 109 3, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, or a range consisting of any two of the above numerical values.

[0183] In some embodiments, 0.85≦a≦0.95.

[0184] a may be 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, or a range consisting of any two of the above values. By combining the above positive electrode active material system with the above electrolyte and the negative electrode plate, the power performance of the battery cell can be significantly improved.

[0185] In some embodiments, b is 0.01, 0.02, 0.05, 0.08, 0.10, 0.12, 0.15, 0.18, 0.20, 0.22, 0.25, 0.28, 0.30, 0.32, 0.35, 0.38, 0.40, 0.42, 0.45, 0.48, 0.50, 0.52, 0.55, 0.58, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, or a range consisting of any two of the above numerical values.

[0186] In some embodiments, c is 0.01, 0.02, 0.05, 0.08, 0.10, 0.12, 0.15, 0.18, 0.20, 0.22, 0.25, 0.28, 0.30, 0.32, 0.35, 0.38, 0.40, 0.42, 0.45, 0.48, 0.50, 0.52, 0.55, 0.58, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, or a range consisting of any two of the above numerical values.

[0187] In some embodiments, a+b+c may be 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, or a range consisting of any two of the foregoing values.

[0188] In some embodiments, z can be 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, or a range consisting of any two of the foregoing values.

[0189] In the charging and discharging process, the battery is accompanied by the absorption, release and consumption of active ions, such as Li, and the battery has different molar contents of Li when discharged to different states. In the embodiments of the present application, in the listing of the positive electrode active materials, the molar contents of Li are those in the initial state of the material, i.e., the state before the material is added, and when the positive electrode active material is used in a battery system and goes through charge and discharge cycles, the molar contents of Li may change.

[0190] In the enumeration of the positive electrode active materials in the embodiments of the present application, the molar content of oxygen O is merely a theoretical state value, and the molar content of oxygen O changes due to oxygen release from the lattice, and in reality, the molar content of oxygen O fluctuates.

[0191] In some embodiments, the M element includes at least one of titanium (Ti) and zirconium (Zr), and optionally, M includes Ti and Zr elements, both of which can enhance cycle performance.

[0192] In some embodiments, the total mass content of Ti and Zr is 1600 ppm to 3150 ppm based on the total mass of the positive electrode active material. When the amount of Ti and Zr added is within the above range, the crystal structure of the positive electrode active material can be further improved, and the cycle performance can be improved.

[0193] The total mass content of Ti and Zr elements is the ratio of the total mass of Ti and Zr elements to the total mass of the positive electrode active material.

[0194] Exemplarily, the total mass content of Ti and Zr elements may be 1600 ppm, 1700 ppm, 1800 ppm, 1900 ppm, 2000 ppm, 2100 ppm, 2200 ppm, 2300 ppm, 2400 ppm, 2500 ppm, 2600 ppm, 2700 ppm, 2800 ppm, 2900 ppm, 3000 ppm, 3100 ppm, 3150 ppm, or a range consisting of any two of the above values.

[0195] In some embodiments, the mass content of Ti element based on the total mass of the positive electrode active material is 100 ppm to 600 ppm, for example, 100 ppm, 200 ppm, 300 ppm, 400 ppm, 450 ppm, 500 ppm, 600 ppm, or a range consisting of any two of the above values.

[0196] In some embodiments, the mass content of Zr element based on the total mass of the positive electrode active material is 500 ppm to 2550 ppm, and optionally 1500 ppm to 2550 ppm, for example, 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm, 1100 ppm, 1200 ppm, 1300 ppm, 1400 ppm, 1500 ppm, 1600 ppm, 1700 ppm, 1800 ppm, 1900 ppm, 2000 ppm, 2100 ppm, 2200 ppm, 2300 ppm, 2400 ppm, 2500 ppm, 2550 ppm, or a range consisting of any two of the above numerical values.

[0197] In some embodiments, at least one of lithium difluoro(oxalato)borate LiDFOB and lithium tetrafluoroborate LiBF4 in the electrolyte can provide fluorine ions and boron ions. In the later stage of the battery cycle, metal ions in the positive electrode active material, such as Ti and Zr ions, have a risk of dissolving into the electrolyte and migrating to the surface of the negative electrode plate, while fluorine ions and boron ions have a relatively strong binding ability with the metal ions, which can reduce the risk of the metal ions migrating to the surface of the negative electrode plate, improve the cycle performance of the battery, and also compensate for the power deterioration caused by Ti and Zr ions.

[0198] In some embodiments, the positive electrode active material comprises at least one of single crystal particles and polycrystalline particles. The positive electrode active material system in combination with the electrolyte and negative electrode plate can significantly improve the power performance of a battery cell.

[0199] In some embodiments, the cathode active material comprises a single crystal particle, the single crystal particle comprising an inner region and an outer region, the outer region extending 500 nm from any point on an outer surface of the single crystal particle directly into the single crystal material, and the M element comprises aluminum Al, the aluminum Al being distributed in at least the outer region.

[0200] The inner region of the single crystal particle may be understood as the core of the single crystal particle, the outer region is coated on the outside of the inner region, and there may be no clear boundary between the outer region and the inner region, and the outer region and the inner region may be considered as two artificially defined regions, the outer region is a region extending 500 nm from any one point on the outer surface of the single crystal particle toward the inside of the single crystal particle, and the extension path is a straight path, and the outer region may be understood as a ring structure, and the radial pitch of the ring structure is 500 nm or less.

[0201] In some embodiments, the active cathode material includes single crystal particles and polycrystalline particles. The active cathode material system in combination with the electrolyte and anode plate can significantly improve the power performance of a battery cell.

[0202] The aluminum Al element is distributed at least in the outer region, which contributes to the formation of aluminum oxide Al2O3 in the positive electrode active material and passivates the side reaction between the positive electrode active material and the electrolyte, thereby further improving the structural stability of the positive electrode active material and improving the cycle performance of the battery. Of course, the Al element is not only distributed in the outer region, but the Al element may also be distributed in the inner region.

[0203] In some embodiments, the mass content of Al element is 500 ppm to 3000 ppm, and optionally 1000 ppm to 2000 ppm, based on the total mass of the positive electrode active material.

[0204] For example, the mass content of Al element may be 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm, 1100 ppm, 1200 ppm, 1300 ppm, 1400 ppm, 1500 ppm, 1600 ppm, 1700 ppm, 1800 ppm, 1900 ppm, 2000 ppm, or a range consisting of any two of the above numerical values.

[0205] In some embodiments, the combination of lithium difluorophosphate LiPO2F2 in the electrolyte and element Al in the positive electrode active material can improve the DCR on the surface of the positive electrode active material and enhance the interfacial power.

[0206] In some embodiments, the M element includes at least one of phosphorus (P), sulfur (S), and boron (B), and optionally, the M element includes phosphorus (P), sulfur (S), and boron (B). The phosphorus (P), sulfur (S), and boron (B) elements can enhance the structural stability of the positive electrode active material and improve the cycle performance of the battery.

[0207] In some embodiments, based on the total mass of the positive electrode active material, the total mass content of P, S and B elements is 0 to 800 ppm, and optionally 10 ppm to 500 ppm, such as 0, 10 ppm, 20 ppm, 30 ppm, 40 ppm, 50 ppm, 60 ppm, 80 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, 350 ppm, 400 ppm, 450 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, or a range consisting of any two of the above values. When the total mass content of P, S and B elements is 0, it means that such elements are not added.

[0208] In some embodiments, the total mass content of the P element based on the total mass of the positive electrode active material is 10 ppm to 500 ppm, for example, 10 ppm, 20 ppm, 30 ppm, 40 ppm, 50 ppm, 60 ppm, 80 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, 350 ppm, 400 ppm, 450 ppm, 500 ppm, or a range consisting of any two of the above numerical values.

[0209] In some embodiments, the total mass content of the S element based on the total mass of the positive electrode active material is 10 ppm to 500 ppm, for example, 10 ppm, 20 ppm, 30 ppm, 40 ppm, 50 ppm, 60 ppm, 80 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, 350 ppm, 400 ppm, 450 ppm, 500 ppm, or a range consisting of any two of the above numerical values.

[0210] In some embodiments, the total mass content of the B element based on the total mass of the positive electrode active material is 10 ppm to 500 ppm, for example, 10 ppm, 20 ppm, 30 ppm, 40 ppm, 50 ppm, 60 ppm, 80 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, 350 ppm, 400 ppm, 450 ppm, 500 ppm, or a range consisting of any two of the above numerical values.

[0211] In some embodiments, the electrolyte additive may further include lithium fluorosulfonate, which can form a low impedance film component on the surface of the positive electrode active material, and the combination of lithium fluorosulfonate with the phosphorus (P), sulfur (S) and boron (B) elements in the positive electrode active material can reduce the DCR on the surface of the positive electrode active material and increase the interfacial power.

[0212] In the embodiment of the present application, the content of elements in the positive electrode active material is a meaning known in the art, and can be detected using instruments and methods known in the art, for example, by inductively coupled plasma atomic emission spectroscopy with reference to EPA 6010D-2014, and measured using plasma atomic emission (ICP-OES, instrument model number: Thermo ICAP7400). First, 0.4 g of the positive electrode active material is weighed out, and 10 ml (50% concentration) aqua regia is added thereto. Then, the mixture is left on a tablet at 180°C for 30 minutes. After digestion on the tablet, the volume is adjusted to 100 mL, and a quantitative test is performed using a calibration curve method.

[0213] In some embodiments, the positive electrode film layer further optionally includes a positive electrode conductive agent. The embodiments of the present application are not particularly limited to the type of the positive electrode conductive agent, and for example, the positive electrode conductive agent includes at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, based on the total mass of the positive electrode film layer, the mass content of the positive electrode conductive agent is ≦5%.

[0214] In some embodiments, the positive electrode membrane layer further optionally includes a positive electrode adhesive. The embodiments of the present application are not particularly limited to the type of the positive electrode adhesive, and for example, the positive electrode adhesive may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin. In some embodiments, based on the total mass of the positive electrode membrane layer, the mass content of the positive electrode adhesive is ≦5%.

[0215] In some embodiments, the ratio of the compaction density of the positive electrode membrane layer to the compaction density of the negative electrode membrane layer is (2 to 2.5): 1, such as 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, or a range consisting of any two of the foregoing values.

[0216] In some embodiments, the packed density PD of the positive electrode membrane layer is 3 g / cm 3 ~3.5g / cm 3 For example, 3g / cm 3 , 3.1g / cm 3 , 3.2g / cm 3 , 3.3g / cm 3 , 3.4g / cm 3 , 3.5g / cm 3 Or it is a range consisting of any two of the above values.

[0217] In the embodiment of the present application, the compaction density of the positive electrode active material layer is a meaning known in the art, and can be tested by a method known in the art. For example, a positive electrode plate that has been coated on one side and cold pressed (if the positive electrode plate is coated on both sides, the positive electrode film on one side can be wiped off first) is taken, punched into a small wafer with an area of ​​S1, and its weight is recorded as M1. Then, the positive electrode film of the weighed positive electrode plate is wiped off, and the weight of the positive electrode current collector is weighed and recorded as M0, where the areal density of the positive electrode active material layer=(weight of the positive electrode plate M1-weight of the positive electrode current collector M0) / S1, and the compaction density of the positive electrode active material layer=area density of the positive electrode active material layer / thickness of the positive electrode active material layer.

[0218] In some embodiments, the positive electrode current collector may be a metal foil sheet or a composite current collector. An example of the metal foil sheet may be aluminum foil. The composite current collector may include a polymer base layer and a metal material layer formed on at least one surface of the polymer base layer. For example, the metal material of the metal material layer may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. For example, the polymer base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0219] In some embodiments, the thickness of the positive electrode current collector is less than or equal to 13 μm, optionally between 8 μm and 13 μm, and optionally between 10 μm and 13 μm.

[0220] The thickness of the positive electrode current collector is relatively thin, which can weaken the heat dissipation path of the battery and reserve some heat within the battery cell under low SOC discharge conditions, which is favorable for improving the DCR at low SOC, and thereby improving the discharge power at low SOC.

[0221] For example, the thickness of the positive electrode current collector may be 8 μm, 8.2 μm, 8.5 μm, 8.8 μm, 9.0 μm, 9.2 μm, 9.5 μm, 9.6 μm, 9.8 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, or a range consisting of any two of the above numerical values.

[0222] In the embodiment of the present application, the thickness of the positive electrode current collector has a meaning known in the art and can be detected using an instrument and a method known in the art, for example, a positive electrode plate is used as a sample, the positive electrode film layer on the surface of the positive electrode plate is washed with an organic solvent such as alcohol, and the thickness of the positive electrode current collector is measured with a multimeter.

[0223] The positive electrode film layer is generally obtained by applying a positive electrode slurry onto a positive electrode current collector, drying, and cold pressing. The positive electrode slurry is generally formed by dispersing a positive electrode active material, an optional conductive agent, an optional adhesive, and any other components in a solvent and stirring the mixture uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP).

[0224] In some embodiments, the positive electrode plate, the separator and the negative electrode plate can be manufactured into an electrode assembly by a winding process and / or a stacking process, and the electrode assembly can be understood as being a wound electrode assembly or a stacked electrode assembly, and optionally, the electrode assembly is a stacked electrode assembly, which can provide closer contact between the positive electrode plate and the negative electrode plate and further improve the DCR.

[0225] In some embodiments, the battery may include an exterior body that may be used to package the electrode assembly and electrolyte.

[0226] In some embodiments, the battery exterior may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The battery exterior may be a pouch, such as a bag-like pouch. The pouch may be made of plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0227] The embodiment of the present application is not particularly limited to the shape of the battery, which may be cylindrical, rectangular, or any other shape. Figure 1 shows a battery cell 5 with a rectangular structure as an example.

[0228] In some embodiments, as shown in FIG. 2, the exterior body may include a case 51 and a cover plate 53. The case 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround and form a receiving cavity. The case 51 has an opening communicating with the receiving cavity, and the cover plate 53 is used to cover the opening and seal the receiving cavity. The positive electrode plate, the negative electrode plate and the separator may be wound and / or stacked to form an electrode assembly 52. ​​The electrode assembly 52 is packaged in the receiving cavity. An electrolyte is infiltrated into the electrode assembly 52. ​​The number of electrode assemblies 52 included in the battery cell 5 may be one or more, and may be adjusted according to demand.

[0229] The method for manufacturing the battery according to the embodiment of the present application is known. In some embodiments, a battery can be formed by assembling a positive electrode plate, a separator, a negative electrode plate, and an electrolyte. For example, the positive electrode plate, the separator, and the negative electrode plate can be wound and / or stacked to form an electrode assembly, the electrode assembly can be placed in an outer casing, dried, and then injected with an electrolyte. The battery can be obtained by vacuum packaging, standing, chemical conversion, shaping, and other processes.

[0230] In some examples of the embodiments of the present application, the batteries according to the embodiments of the present application may be assembled into a battery module, and the number of batteries included in the battery module may be multiple, and the specific number may be adjusted according to the application and capacity of the battery module.

[0231] Fig. 3 is a schematic diagram of an example battery module 4. As shown in Fig. 3, in the battery module 4, a plurality of battery cells 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, the battery cells 5 may be arranged in any other manner. Furthermore, the plurality of battery cells 5 may be fixed by fasteners.

[0232] Optionally, the battery module 4 may further include a housing having an accommodating space, and the multiple battery cells 5 are accommodated in the accommodating space.

[0233] In some embodiments, the above battery modules may be further assembled into a battery pack, and the number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0234] 4 and 5 are schematic diagrams of an example battery pack 1. As shown in FIGS. 4 and 5, the battery pack 1 may include a battery box and a plurality of battery modules 4 installed in the battery box. The battery box includes an upper housing 2 and a lower housing 3, and the upper housing 2 is used to cover the lower housing 3 and form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0235] power consumption equipment A third aspect of the present application provides a power consuming device, the power consuming device including at least one of the batteries, battery modules, or battery packs of the present application. The battery, battery module, or battery pack may be used as a power source for the power consuming device, or may be used as an energy storage unit for the power consuming device. The power consuming device may be, but is not limited to, a mobile device (e.g., mobile phone, laptop, etc.), an electric vehicle (e.g., pure electric vehicle, hybrid electric vehicle, plug-in hybrid electric vehicle, electric bicycle, electric scooter, electric golf cart, electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.

[0236] A power consuming device can select a battery, a battery module or a battery pack according to its usage needs.

[0237] 6 is a schematic diagram of an example power consumer 6, which may be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the high power and high energy density demands of the power consumer 6, a battery pack or battery module may be employed.

[0238] Another example of the power consuming device may be a mobile phone, a tablet computer, a notebook computer, etc. The power consuming device generally requires a thin design and may employ a battery as a power source.

[0239] Working Example The following examples more specifically describe the contents disclosed in the embodiments of the present application, and these examples are merely descriptive, since it is obvious to those skilled in the art that various modifications and changes can be made within the scope of the contents disclosed in the embodiments of the present application.Unless otherwise specified, all parts, percentages and ratios reported in the following examples are all based on mass, and all reagents used in the examples are commercially available or can be synthesized and obtained by conventional methods, and can be used directly without further treatment, and all instruments used in the examples are commercially available.

[0240] Example 1 1. Manufacturing of positive electrode plates The positive electrode plate includes a positive electrode collector and a positive electrode film layer. The positive electrode collector is an aluminum foil having a thickness of 10 μm. The positive electrode film layer includes a film layer formed by uniformly coating a positive electrode slurry (solvent is N-methylpyrrolidone (NMP)) on the surface of the aluminum foil positive electrode collector, drying, and cold pressing. The positive electrode film layer includes a positive electrode active material in a weight ratio of 97.5:1.4:1.1, a conductive agent of carbon black, and an adhesive of polyvinylidene fluoride (PVDF).

[0241] The positive electrode active material has a single crystal structure and has the molecular formula Li d Ni a Co b Mn c M (1-a-b-c) O z wherein the nickel cobalt manganese oxide substrate in the positive electrode active material has the molecular formula LiNi 0.70 Co 0.10 Mn 0.20 Contains compounds of O2.

[0242] The M elements include 450 ppm Ti, 1700 ppm Zr, 1600 ppm Al, and 120 ppm (B, S, and P) elements.

[0243] 2. Manufacturing of negative electrode plates The negative electrode plate includes a negative electrode collector and a negative electrode film layer. The negative electrode collector is a copper foil having a thickness of 4.5 μm. The negative electrode film layer includes a film layer formed by uniformly coating a negative electrode slurry (solvent is deionized water) on the surface of the negative electrode collector copper foil, drying, and cold pressing. The negative electrode film layer includes a negative electrode active material in a weight ratio of 96.2:1.8:1.2:0.8, styrene butadiene rubber (SBR) as an adhesive, sodium carboxymethylcellulose (CMC-Na) as a thickener, and carbon black (Super P) as a conductive agent.

[0244] The negative electrode active material is 97% artificial graphite and 3% silicon oxide (SiO x The mass content of silicon relative to the total mass of the negative electrode active material is 1.91%.

[0245] 3. Separator The separator can be purchased directly from Ningde Zhuo High-Tech Materials Technology Co., Ltd. The porosity of the separator is 30%, the separator includes an organic substrate (porous polypropylene PP (7 μm)) and a coating, the coating includes a ceramic layer (1 μm) and a polyacrylate layer (1 μm), the ceramic layer is disposed on two surfaces of the organic substrate, the ceramic layer includes a membrane layer formed by dissolving an adhesive and inorganic aluminum oxide in N-methylpyrrolidone (NMP) and applying the solution on the organic substrate, the polyacrylate layer is disposed on the surface of the ceramic layer away from the organic substrate, and the polyacrylate layer is a membrane layer formed by applying a material containing a polyacrylate system on the surface of the ceramic layer.

[0246] 4. Electrolyte production The electrolyte includes an organic solvent, a lithium salt, and an additive, the organic solvent includes a cyclic carbonate (EC, PC, and BC, the mass ratio of each component is 1:1:1) and a chain carbonate (EMC, DMC, and DEC, the mass ratio of each component is 1:1:1), the additive includes monofluoroethylene carbonate FEC, and the additive further includes at least one of PS, VC, and LiSO3F, the total content of which is ≦2%.

[0247] 5. Battery manufacturing The positive electrode plate, separator and negative electrode plate are stacked in order, and a separator is placed between the positive electrode plate and the negative electrode plate to perform isolation, and then wound to obtain an electrode assembly. The electrode assembly is placed in an outer case and dried, and then an electrolyte is injected. After vacuum packaging, standing, chemical formation, shaping and other processes, a lithium ion battery is obtained. The liquid retention coefficient of the lithium ion battery is 2.0g / Ah.

[0248] Comparative Example 1 A lithium ion battery was manufactured using a method similar to that of Example 1. The difference from Example 1 is that the negative electrode active material of Comparative Example 1 is different. The negative electrode active material is 94% artificial graphite and 6% silicon oxide SiO. x and the mass content of silicon is 3.82%.

[0249] Comparative Example 2 and Comparative Example 3 Lithium ion batteries were manufactured using a method similar to that of Example 1. The difference from Example 1 is that Comparative Example 2 and Comparative Example 3 adjusted the components of the electrolyte, especially the content of lithium hexafluorophosphate.

[0250] Comparative Example 4 A lithium ion battery was manufactured using a method similar to that of Example 1, except that the negative electrode active material of Comparative Example 4 was different and contained 100% artificial graphite.

[0251] Examples 2-1 to 2-5 Lithium ion batteries were manufactured using a method similar to that of Example 1, and the difference from Example 1 is that in Examples 2-1 to 2-5, at least the composition of the negative electrode active material was adjusted.

[0252] Examples 3-1 to 3-3 Lithium ion batteries were manufactured using a method similar to that of Example 1, and the difference from Example 1 is that in Examples 3-1 to 3-3, at least the composition of the negative electrode active material was adjusted.

[0253] Example 4 to Example 4-2 Lithium ion batteries were manufactured using a method similar to that of Example 1, and the difference from Example 1 is that in Examples 4 to 4-2, at least the composition of the electrolyte, particularly the mass content of lithium hexafluorophosphate, was adjusted.

[0254] Examples 5-1 to 5-7 Lithium ion batteries were manufactured using a method similar to that of Example 1, and the difference from Example 1 is that Examples 5-1 to 5-7 adjusted at least the composition of the electrolyte, particularly the mass content of at least one of the cyclic ester and the linear carbonate.

[0255] Examples 6-1 to 6-4 Lithium ion batteries were manufactured using a method similar to that of Example 1, and the difference from Example 1 is that in Examples 6-1 to 6-4, at least the composition of the electrolyte, particularly the mass content of the fluorinated cyclic carbonate, was adjusted.

[0256] Example 7 A lithium ion battery was manufactured using a method similar to that of Example 1. The difference from Example 1 is that Example 7 adjusts at least the composition of the electrolyte, particularly the type of fluorinated cyclic carbonate, to DFEC, which contains two fluorine atoms, has relatively weak polarity, and is relatively difficult to form a film with compared with FEC.

[0257] Examples 8-1 to 8-4 Lithium ion batteries were manufactured using a method similar to that of Example 1, and the difference from Example 1 is that in Examples 8-1 to 8-4, at least the retention coefficient of the electrolyte was adjusted.

[0258] Examples 9-1 to 9-4 Lithium ion batteries were manufactured using a method similar to that of Example 1, and the difference from Example 1 is that Examples 9-1 to 9-4 adjusted at least one of the coating thickness and the porosity of the separator.

[0259] Examples 9-3 and 9-4 use PP materials with different porosities, and the different porosities can be adjusted by methods known to those skilled in the art.

[0260] The parameters of the examples and comparative examples are as shown in Tables 1 to 3.

[0261] Performance Testing 1. Lithium-ion battery DC internal resistance (DCR) test Capacity test flow: In an environment of 25°C, the lithium ion batteries manufactured in the examples and comparative examples were first discharged to 2.8V at 0.33C, then charged to 4.35V at 0.33C, charged at 4.35V at a constant voltage until the current value was less than 0.05C, and then discharged to 2.8V at 0.33C. The discharge capacity at this time was recorded as the true capacity D0 of the battery. 10%SOC adjustment: Charge the lithium-ion battery at 0.1C (where C is determined by the D0 being tested) for 6 minutes to adjust it to 10% SOC, record the voltage value at this time as U1, and discharge it at 4C for 10s, record the voltage value at this time as U2, DC internal resistance DCR = (U1-U2) / I.

[0262] Test results The test results are shown in Tables 1 to 3.

[0263] [Table 1] JPEG2025507262000003.jpg252170 JPEG2025507262000004.jpg79170

[0264] [Table 2] JPEG2025507262000006.jpg252160JPEG2025507262000007.jpg252156JPEG2025507262000008.jpg25284

[0265] [Table 3] JPEG2025507262000010.jpg252157JPEG2025507262000011.jpg252160

[0266] As can be seen from Tables 1 to 3, Both Comparative Example 1 and Comparative Example 4 adopted appropriate electrolyte systems, but the mass content of silicon element in Comparative Example 1 was relatively high, and even if the system contained lithium hexafluorophosphate with a relatively high content, it could not well alleviate the volume expansion of the silicone-based material, and the risk of the silicone-based material collapsing and bursting into powder was relatively high, which was unfavorable to improving DCR, and the battery discharge power was relatively poor. Comparative Example 4 adopted artificial graphite as the negative electrode active material, but at low SOC, artificial graphite was not easily involved in discharge, and was prone to discharge deficiency, resulting in relatively poor discharge power.

[0267] Comparative Example 2 and Comparative Example 3 both adopted appropriate silicon material systems. However, Comparative Example 2 adopted a lithium hexafluorophosphate with a relatively low content (12%). The lithium hexafluorophosphate with a relatively low content produced relatively little fluorine lithium compound on the surface of the negative electrode active material, and was unable to effectively alleviate the problem of the silicone-based material exploding and powdering. Comparative Example 3 adopted a lithium hexafluorophosphate with a relatively high content (23%). The lithium hexafluorophosphate with a relatively high content could effectively alleviate the volume expansion of the silicone-based material. However, the lithium hexafluorophosphate made the viscosity of the electrolyte system too high, which was unfavorable to the migration of lithium ions from the negative electrode surface to the positive electrode surface, and made it difficult to improve the discharge power in the later stage of discharge.

[0268] Compared to Comparative Examples 1 to 4, Example 1 adjusts the silicon content (mass content of silicon element is 0.3% or more and 3.0% or less) in the silicon oxide of the negative electrode active material and combines it with an appropriate electrolyte system (mass content of lithium hexafluorophosphate is 15% to 20%), thereby reducing the internal resistance of the battery at the end of discharge and improving the discharge power performance.

[0269] The content of silicon element has a certain effect on the discharge power of the battery, and the amount of silicon element added is small, and the amount of negative electrode active material involved in the later discharge is relatively small, which is unfavorable to the improvement of the discharge power of the battery. The amount of silicon element added is large, and the unfavorable effect of volume expansion gradually appears. Therefore, by selecting an appropriate content of silicon element, it is more favorable to the improvement of the discharge power of the battery. For example, when the mass content of silicon element in silicon oxide is more than 0.3% and less than 3.0%, the discharge power of the battery can be significantly increased. The materials of silicone-based materials and carbon-based materials also have a certain effect on the discharge power. The components of the electrolyte also have a certain effect on the discharge power.

[0270] Example 10-1 1. Manufacturing of positive electrode plates The positive electrode plate includes a positive electrode collector and a positive electrode film layer. The positive electrode collector is an aluminum foil having a thickness of 12 μm. The positive electrode film layer includes a film layer formed by uniformly coating a positive electrode slurry (solvent is N-methylpyrrolidone (NMP)) on the surface of the positive electrode collector aluminum foil, drying, and cold pressing. The positive electrode film layer includes a positive electrode active material in a weight ratio of 97.5:1.4:1.1, a conductive carbon black, and an adhesive polyvinylidene fluoride (PVDF). The compaction density of the positive electrode film layer is 3.35 g / cm. 3 It is.

[0271] The positive electrode active material has a single crystal structure and has the molecular formula Li d Ni a Co b Mn c M (1-a-b-c) O z wherein the nickel cobalt manganese oxide substrate in the positive electrode active material has the molecular formula LiNi0.70 Co 0.10 Mn 0.20 The M element contains 450 ppm Ti, 1700 ppm Zr, 1600 ppm Al, and 120 ppm (B, S, and P) elements.

[0272] 2. Manufacturing of negative electrode plates The negative electrode plate includes a negative electrode collector and a negative electrode film layer. The negative electrode collector is a copper foil having a thickness of 4.5 μm. The negative electrode film layer includes a film layer formed by uniformly coating a negative electrode slurry (solvent is deionized water) on the surface of the negative electrode collector copper foil, drying, and cold pressing. The negative electrode film layer includes a negative electrode active material in a weight ratio of 96.2:1.8:1.2:0.8, a styrene butadiene rubber (SBR) adhesive, a thickener sodium carboxymethylcellulose (CMC-Na), and a conductive carbon black (Super P).

[0273] The negative electrode active material includes artificial graphite and a silicon-carbon composite.

[0274] 3. Separator The separator can be purchased directly from a separator supplier. The porosity of the separator is 30%, the separator includes an organic substrate (porous polypropylene PP (7 μm)) and a coating, the coating includes a ceramic layer (1 μm) and a polyacrylate layer (1 μm), the ceramic layer is disposed on two surfaces of the organic substrate, the ceramic layer includes a membrane layer formed by dissolving an adhesive and inorganic aluminum oxide in N-methylpyrrolidone (NMP) and applying the solution on the organic substrate, the polyacrylate layer is disposed on the surface of the ceramic layer away from the organic substrate, and the polyacrylate layer is a membrane layer formed by applying a material containing a polyacrylate system on the surface of the ceramic layer.

[0275] 4. Electrolyte production The electrolyte contains an organic solvent, a lithium salt, and an additive. The organic solvent contains cyclic carbonate (EC, PC, and BC, the mass ratio of each component is 1:1:1) and linear carbonate (EMC, DMC, and DEC, the mass ratio of each component is 1:1:1). The additive contains 0.25% monofluoroethylene carbonate (FEC). The lithium salt contains 18.2% lithium hexafluorophosphate, 0.2% lithium difluorophosphate, and 0.2% lithium tetrafluoroborate. The total content of the lithium salt is 18.6%, and the rest is an organic solvent.

[0276] 5. Battery manufacturing The positive electrode plate, separator and negative electrode plate are stacked in order, and a separator is placed between the positive electrode plate and the negative electrode plate to perform isolation, and then wound to obtain an electrode assembly. The electrode assembly is placed in an outer case and dried, and then an electrolyte is injected. After vacuum packaging, standing, chemical formation, shaping and other processes, a lithium ion battery is obtained. The liquid retention coefficient of the lithium ion battery is 1.3g / Ah.

[0277] Examples 10-2 to 10-4 A lithium ion battery was manufactured using a method similar to that of Example 10-1, except that the content of each negative active material in the negative electrode plate was adjusted.

[0278] Example 11 and Example 11-2 A lithium ion battery was prepared using a method similar to that of Example 10-1, with the difference being that the mass content of monofluoroethylene carbonate (FEC) in the electrolyte was adjusted.

[0279] Detection was performed using the test methods in Tables 1 to 3, and the test results are shown in Table 4.

[0280] [Table 4]

[0281] As can be seen from Table 4, in Examples 10-1 to 11-2, the silicon content (mass content of silicon element in silicon-carbon composite is 0.3% or more and 10% or less) is adjusted, and an appropriate electrolyte system (mass content of lithium hexafluorophosphate is 15% to 20%) is combined, thereby significantly reducing the internal resistance of the battery at the end of discharge and improving the discharge power performance. By adjusting the mass content of the fluorinated cyclic carbonate, the internal resistance of the battery at the end of discharge can be adjusted and the discharge power performance can be improved.

[0282] Although illustrative embodiments have been demonstrated and described, it should be understood by those skilled in the art that the above embodiments should not be construed as limitations on the present application, and that the embodiments can be changed, substituted, and modified without departing from the spirit, principles, and scope of the present application. [Explanation of symbols]

[0283] The explanation of the symbols is as follows. 1, battery pack, 2, upper housing, 3, lower housing, 4, battery module, 5, battery cell, 51, case, 52, electrode assembly, 53, cover plate, 6, power consumption equipment.

Claims

1. A battery cell, an electrolyte solution containing a lithium salt, the lithium salt including lithium hexafluorophosphate, the mass content of the lithium hexafluorophosphate being 15% to 20% relative to the total mass of the electrolyte solution; a positive electrode plate including a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector and containing a positive electrode active material; A negative electrode plate including a negative electrode current collector and a negative electrode film layer disposed on at least one side of the negative electrode current collector and containing a negative electrode active material, the negative electrode active material further including a carbon-based material and a silicon-carbon composite, and a mass content of silicon in the silicon-carbon composite relative to a total mass of the negative electrode active material is 0.3% or more and 10.0% or less; a separator disposed between the positive electrode plate and the negative electrode plate.

2. 2. The battery cell according to claim 1, wherein the mass content of silicon element in the silicon-carbon composite relative to the total mass of the negative electrode active material is 4.0% or more and 7.0% or less.

3. 3. The battery cell according to claim 1, wherein the mass content of the silicon-carbon composite is 0.4% to 14.5% based on the total mass of the negative electrode active material.

4. The battery cell of claim 3 , wherein the mass content of the silicon-carbon composite is 5.75% to 10%, based on the total mass of the negative electrode active material.

5. The battery cell according to claim 1 , wherein the carbon-based material includes at least one of artificial graphite and natural graphite.

6. The battery cell of claim 5 , wherein the carbon-based material comprises synthetic graphite.

7. The battery cell according to any one of claims 1 to 6, wherein the electrolyte further contains a cyclic carbonate, and the ratio of the mass content of the cyclic carbonate to the mass content of the lithium hexafluorophosphate based on the total mass of the electrolyte is (0.60 to 2.50):

1.

8. 8. The battery cell according to claim 7, wherein the ratio of the mass content of the cyclic carbonate to the mass content of the lithium hexafluorophosphate is (1.00-1.65):

1.

9. the mass content of the cyclic carbonate is between 10% and 41%; and / or 9. The battery cell according to claim 7 or 8, wherein the cyclic carbonate includes at least one of ethylene carbonate, propylene carbonate, and butylene carbonate.

10. The battery cell according to claim 9 , wherein the mass content of the cyclic carbonate is 20% to 30%.

11. The battery cell according to any one of claims 7 to 10, wherein the electrolyte further contains a chain carbonate, and the ratio of the mass content of the chain carbonate to the mass content of the cyclic carbonate, based on the total mass of the electrolyte, is (0.9 to 6):

1.

12. The battery cell according to claim 11, wherein the ratio of the mass content of the chain carbonate to the mass content of the cyclic carbonate is (1.5 to 2.65):

1.

13. the mass content of the linear carbonate is between 35% and 65%; and / or The battery cell according to claim 11 or 12, wherein the chain carbonate includes at least one of ethyl methyl carbonate, diethyl carbonate, and dimethyl carbonate.

14. The battery cell of claim 1 , wherein the electrolyte further comprises a fluorinated cyclic carbonate.

15. 15. The battery cell of claim 14, wherein the fluorinated cyclic carbonate includes at least one of monofluoroethylene carbonate, bisfluoroethylene carbonate, and trifluoropropylene carbonate.

16. the fluorinated cyclic carbonate comprises monofluoroethylene carbonate; and / or 16. The battery cell according to claim 15, wherein a ratio of a mass content of the fluorinated cyclic carbonate to a mass content of the silicon element relative to a total mass of the electrolyte is (0.01-9.5):

1.

17. 17. The battery cell according to claim 16, wherein a ratio of a mass content of the fluorinated cyclic carbonate to a mass content of the silicon element relative to a total mass of the electrolyte is (0.01-0.15):

1.

18. The ratio of the mass content of the fluorinated cyclic carbonate to the mass content of the lithium salt based on the total mass of the electrolyte is (0.005 to 0.30):

1. The battery cell according to any one of claims 14 to 17.

19. The battery cell according to claim 18, wherein the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of the lithium salt is (0.005-0.03):1, based on the total mass of the electrolyte.

20. The battery cell according to any one of claims 14 to 17, wherein the mass content of the fluorinated cyclic carbonate is 0.05% to 5.80% based on the total mass of the electrolyte.

21. The battery cell according to claim 20, wherein the mass content of the fluorinated cyclic carbonate is 0.1% to 1.0%, based on the total mass of the electrolyte.

22. 22. The battery cell of claim 1, wherein the lithium salt further comprises at least one of a fluorine-containing inorganic phosphate and a fluorine-containing inorganic borate.

23. Based on the total mass of the electrolyte, the mass content of the fluorine-containing inorganic phosphate is 0.05% to 0.50%; and / or 23. The battery cell according to claim 22, wherein the mass content of the fluorine-containing inorganic borate is 0.05% to 0.50%, based on the total mass of the electrolyte.

24. the mass content of the fluorine-containing inorganic phosphate is between 0.10% and 0.30%; and / or 24. The battery cell of claim 23, wherein the mass content of the fluorine-containing inorganic borate is 0.10% to 0.30%.

25. The fluorine-containing inorganic phosphate is lithium difluorophosphate LiPO 2 F 2 and / or The fluorine-containing inorganic borate is lithium tetrafluoroborate LiBF 4 and lithium difluoro(oxalato)borate LiDFOB.

26. The battery cell according to any one of claims 1 to 25, wherein the battery cell has a electrolyte retention coefficient of 1.0 g / Ah to 2.5 g / Ah.

27. The battery cell according to claim 26, wherein the battery cell has a electrolyte retention coefficient of 1.0 g / Ah to 1.5 g / Ah.

28. The battery cell according to any one of claims 1 to 27, wherein the porosity of the separator is 30% to 40%.

29. 29. The battery cell of claim 1, wherein the separator includes an organic substrate and a coating disposed on at least one side of the organic substrate, the coating including a heat-resistant layer and an organic layer, the heat-resistant layer being disposed on a surface of the organic substrate, and the organic layer being disposed on a surface of the heat-resistant layer that is away from the organic substrate.

30. 30. The battery cell of claim 29, wherein the organic layer comprises a non-fluorinated polymer.

31. 31. The battery cell of claim 30, wherein the non-fluorinated polymer comprises a polyacrylate layer.

32. the thickness of the organic substrate is between 6.6 μm and 7.6 μm; and / or The battery cell of any one of claims 29 to 31, wherein the coating has a thickness of 1.5 μm to 2.5 μm.

33. The positive electrode active material has the molecular formula Li d Ni a Co b Mn c M (1-a-b-c) Y z wherein 0<d≦2.1, 0.6<a<1, 0<b<1, 0<c<1, and 0.6<a+b+c<1, and 1.8≦z≦3.5; the M element includes at least one element selected from the group consisting of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; and the Y element includes at least one element selected from the group consisting of O and F.

34. 34. The battery cell of claim 33, wherein 0.85≦a≦0.

95.

35. 35. The battery cell of claim 33 or 34, wherein the positive electrode active material includes at least one of single crystal particles and polycrystalline particles.

36. 36. The battery cell of claim 35, wherein the active cathode material includes single crystal particles and polycrystalline particles.

37. A battery comprising the battery cell of any one of claims 1 to 36.

38. 38. A power consuming device comprising the battery of claim 37.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2014082075A